Composition and method for producing organic electroluminescent element

By using solvent compositions with different boiling points in the wet film forming process, the temperature dependence of viscosity is improved, and the boiling point of solvent with low boiling points is set to above 245°C, the problem of insufficient flatness of the organic film in the surrounding area of ​​the dike is solved, and uniformity of film thickness and good flatness of the panel end are achieved.

CN112042275BActive Publication Date: 2025-03-28MITSUBISHI CHEM CORP
View PDF 26 Cites 0 Cited by

Patent Information

Application Number
CN201980029200.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-05-01
Filing Date
2019-04-24
Publication Date
2025-03-28
Estimated Expiration
2039-07-08

AI Technical Summary

Technical Problem

In the wet film formation process, the formed organic film is insufficiently flattened in the area surrounded by the partition, especially at the end of the panel, making it difficult to achieve uniform film thickness and flatness.

Method used

The wet film formation was performed using a composition containing two or more solvents having different boiling points. The temperature dependence of the viscosity was improved by using a solvent with a high boiling point, and the boiling point of the solvent with a low boiling point was 245°C or above to improve the flatness of the film.

Benefits of technology

The uniformity of the film thickness in the area surrounded by the partition is achieved, and good flatness is maintained at the center and end of the panel, solving the problem of insufficient film flatness in the traditional method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112042275B_ABST
    Figure CN112042275B_ABST
Patent Text Reader

Abstract

A composition comprises a functional material and a first solvent and a second solvent, wherein the first solvent is a water-insoluble aromatic solvent, the boiling point of the first solvent is higher than that of the second solvent, the difference between the boiling points of the first solvent and the second solvent is greater than 10°C, the flow activation energy of the first solvent is greater than 22 kJ / mol and less than 35 kJ / mol, the content ratio of the first solvent is 5 to 50% by weight relative to the total amount of the first solvent and the second solvent, and the boiling point of the second solvent is greater than 245°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composition suitable for forming an organic film composed of a functional material, that is, a functional film, in the production of an organic electroluminescent element, and a method for producing an organic electroluminescent element using the composition. Background Art

[0002] Methods for manufacturing organic electroluminescent elements typically involve forming and stacking organic materials using vacuum evaporation. In recent years, research has gained momentum on wet film-forming methods, which utilize inkjet methods or other methods to form and stack organic materials in a solution, as a method with greater material efficiency.

[0003] In the manufacture of organic electroluminescent elements, particularly organic EL displays, using wet film formation, a method has been studied in which each pixel is divided by partitions called banks, and an inkjet method is used to eject an ink containing an organic electroluminescent element-forming composition, which is used to form the organic film constituting the organic electroluminescent element, onto the microscopic regions within the banks. At this time, a technique has been proposed for obtaining a flatter film within the region surrounded by the banks by mixing various surface modifiers into the ink (Patent Documents 1 and 2).

[0004] However, in conventional methods, the flatness of the film in the region surrounded by the banks is insufficient.

[0005] Patent Document 3 discloses a technique of using two or more solvents having different boiling points for the purpose of forming a functional layer having a substantially flat cross-sectional shape after drying and curing.

[0006] Patent Document 1: International Publication No. 2010 / 104183

[0007] Patent Document 2: Japanese Patent Application Laid-Open No. 2002-056980

[0008] Patent Document 3: Japanese Patent Application Laid-Open No. 2015-185640

[0009] When using an inkjet device for coating, inks with excessively high viscosities have problems with ejection, while inks with excessively low viscosities cannot be retained by the nozzle. Therefore, there is a certain range of appropriate viscosity. On the other hand, during the drying process of the liquid film, due to various flows such as liquid movement caused by concentration gradients and Marangoni convection, the shape of the dried film tends to become complex. To control this complex film shape, the viscosity of the ink is increased to a certain extent, slowing the flow rate and thus making it easier to control. However, due to the high viscosity, it is possible to exceed the viscosity range that can be properly ejected as an inkjet ink, making it difficult to adjust the viscosity within the appropriate range. In particular, when the solute dissolved in the ejected ink is mainly low-molecular material, the viscosity of the ink is approximately the same as that of the solvent. Therefore, even if the solvent evaporates to some extent, the viscosity of the ink does not change significantly, which can easily lead to the problem that the dried film is difficult to flatten due to the flow of liquid.

[0010] Even when a plurality of solvents having different boiling points are used as in Patent Document 3, there is still room for improvement in the flatness of the edge of the panel coated with ink. Summary of the Invention

[0011] An object of the present invention is to provide a composition and a method for manufacturing an organic electroluminescent element using the composition, wherein the composition can improve the uniformity of the film thickness in the area surrounded by the bank when forming an organic film constituting the organic electroluminescent element by wet film formation, and can further improve the flatness not only in the center but also at the end of the panel coated with ink.

[0012] The present inventors have discovered that when wet film formation is performed on an organic film constituting an organic electroluminescent element within an area surrounded by banks, by using a solvent having a high temperature dependence of viscosity (flow activation energy) as a solvent with a high boiling point in a composition comprising a mixed solution containing two or more solvents having different boiling points and a functional material, the organic film can be wet-formed within the area surrounded by the banks to achieve improved film thickness uniformity. Furthermore, by setting the boiling point of the low-boiling-point solvent to 245°C or higher, the flatness of the panel can be improved not only in the center but also at the edges.

[0013] That is, the present invention has the following configuration.

[0014] [1] A composition comprising a functional material and a first solvent and a second solvent, wherein the first solvent is a water-insoluble aromatic solvent, the boiling point of the first solvent is higher than the boiling point of the second solvent, the difference between the boiling points of the first solvent and the second solvent is 10°C or more, the flow activation energy of the first solvent is 22 kJ / mol or more and 35 kJ / mol or less, the content of the first solvent is 5 to 50% by weight relative to the total amount of the first solvent and the second solvent, and the boiling point of the second solvent is 245°C or more.

[0015] [2] The composition according to [1], wherein the total content of the first solvent and the second solvent in the composition is 50% by weight or more.

[0016] [3] The composition according to [1] or [2], wherein the molecular weight of the functional material is 50,000 or less.

[0017] [4] The composition according to any one of [1] to [3], wherein the viscosity of the second solvent at 23°C is 5 mPas or less.

[0018] [5] The composition according to any one of [1] to [4], wherein the difference between the boiling point of the first solvent and the boiling point of the second solvent is 30° C. or more.

[0019] [6] The composition according to any one of [1] to [5], wherein the flow activation energy of the first solvent is greater than the flow activation energy of the second solvent by 5 kJ / mol or more.

[0020] [7] The composition according to any one of [1] to [6], wherein the surface tension of the first solvent is 30 mN / m or more.

[0021] [8] The composition according to any one of [1] to [7], wherein the first solvent and the second solvent are each any one of naphthalene, benzoate, and aromatic ether which may have a substituent.

[0022] [9] The composition according to any one of [1] to [7], wherein the first solvent is any one of 2-ethylhexyl benzoate, benzyl benzoate, acetylnaphthalene, dimethyl phthalate, diethyl phthalate, ethylbiphenyl, isopropylbiphenyl, diisopropylbiphenyl, triisopropylbiphenyl, and 2-phenoxyethyl isobutyrate, and the second solvent is any one of methylnaphthalene, ethylnaphthalene, isopropylnaphthalene, methoxynaphthalene, butyl benzoate, amyl benzoate, isoamyl benzoate, diphenylmethane, and benzyltoluene.

[0023]

[10] A method for producing an organic electroluminescent element, comprising the step of wet film formation using the composition according to any one of [1] to [9].

[0024] The composition of the present invention can improve the uniformity of the thickness of the functional film within the region surrounded by the bank and improve the flatness not only in the center of the panel coated with the ink but also at the edges. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram showing a cross section of a structural example of the organic electroluminescent element of the present invention.

[0026] Figure 2 This is a diagram showing the distribution of the light-emitting layer and the blank in Reference Example 1.

[0027] Figure 3 This is a diagram showing the distribution of the light-emitting layer and the blank in Reference Example 2.

[0028] Figure 4 This is a diagram showing the distribution of the light-emitting layer and the blank in Comparative Example 1.

[0029] Figure 5 This is a diagram showing the distribution of the light-emitting layer and the blank in Comparative Example 2.

[0030] Figure 6 This is a diagram showing the distribution of the light-emitting layer and the blank in Comparative Example 3.

[0031] Figure 7 This is a graph showing the distribution of the flatness evaluation of the measurement site 1 in Example 1.

[0032] Figure 8 This is a graph showing the distribution of the flatness evaluation of the measurement site 2 in Example 1.

[0033] Figure 9 This is a graph showing the distribution of the flatness evaluation of the measurement site 1 in Example 2.

[0034] Figure 10 This is a graph showing the distribution of the flatness evaluation of the measurement site 2 in Example 2.

[0035] Figure 11 This is a graph showing the distribution of the flatness evaluation of the measurement site 1 in Example 3.

[0036] Figure 12 This is a graph showing the distribution of the flatness evaluation of the measurement site 1 in Comparative Example 4.

[0037] Figure 13 This is a graph showing the distribution of the flatness evaluation of the measurement site 2 in Comparative Example 4.

[0038] Figure 14 This is a graph showing the distribution of the flatness evaluation of the measurement site 1 in Comparative Example 5.

[0039] Figure 15 This is a graph showing the distribution of the flatness evaluation of the measurement site 2 in Comparative Example 5.

[0040] Figure 16 This is a graph showing the distribution of the flatness evaluation of the measurement site 1 in Comparative Example 6.

[0041] Figure 17 This is a graph showing the distribution of the flatness evaluation of the measurement site 2 in Comparative Example 6. DETAILED DESCRIPTION

[0042] [Composition]

[0043] The composition of the present invention is characterized in that it contains a functional material and a first solvent and a second solvent, the first solvent is a water-insoluble aromatic solvent, the boiling point of the first solvent is higher than the boiling point of the second solvent, the difference between the boiling points of the first solvent and the second solvent is greater than 10°C, the flow activation energy of the first solvent is greater than 22 kJ / mol and less than 35 kJ / mol, the content ratio of the first solvent is 5 to 50% by weight relative to the total amount of the first solvent and the second solvent, and the boiling point of the second solvent is greater than 245°C.

[0044] The solvent contained in the composition of the present invention can be used as an ink that can be ejected from a micro nozzle because the boiling point of the second solvent is 245°C or above, and the boiling point of the first solvent is higher than the boiling point of the second solvent, that is, the boiling points of both solvents are 245°C or above. The composition of the present invention shows a moderately low viscosity at room temperature, but if the temperature drops due to the heat of vaporization during the vacuum drying process, it will cause a sharp increase in viscosity. As a result, the flow rate of the liquid slows down, the film shape can be controlled, and a flat film can be obtained. This effect is more significant in a composition with a low molecular weight solute, which is not prone to viscosity increase even if the solvent evaporates and the solid content concentration of the liquid increases. In addition, because the boiling point of the second solvent with a low boiling point is also above 245°C, the solvent can be prevented from vaporizing before the vacuum drying process even at the end of the panel that dries particularly quickly. Therefore, the temperature can be sufficiently lowered during the vacuum drying process, and a flat film can be obtained.

[0045] In this specification, when the composition of the present invention is used as ink ejected from a nozzle of an inkjet printer or the like, it may be simply referred to as ink.

[0046] When the composition of the present invention is used as ink ejected from a nozzle of an inkjet printer or the like, and is ejected from the nozzle and applied to an area surrounded by a bank, the ink in the area surrounded by the bank is sometimes referred to as a liquid or a liquid film, and the ink ejected from the nozzle is sometimes referred to as a droplet.

[0047] The ink in which the liquid film in the region surrounded by the banks is dried and the solvent composition ratio of the liquid film is changed by evaporation of the solvent is sometimes referred to as liquid or liquid film.

[0048] A film containing a functional material obtained by coating the composition of the present invention, volatilizing the organic solvent, and drying is referred to as a functional film. Furthermore, a film containing an organic compound and no solvent, or substantially obtained by volatilizing the solvent and drying, is referred to as an organic film. A functional film is a type of organic film.

[0049] [Solvent]

[0050] <Type of Solvent>

[0051] In the present invention, from the viewpoint of improving flatness due to a temperature drop and a rapid increase in viscosity and ensuring flatness at the panel edge, solvents having a boiling point of 245° C. or higher are used as the first and second solvents.

[0052] The solvent having a boiling point of 245° C. or higher is not particularly limited, but preferred examples include water-insoluble aromatic solvents such as aromatic hydrocarbon solvents, aromatic ester solvents, aromatic ether solvents, and aromatic ketone solvents.

[0053] As the aromatic hydrocarbon solvent, benzene derivatives, naphthalene derivatives, hydrogenated naphthalene derivatives, and biphenyl derivatives are preferred.

[0054] Preferred benzene derivatives include those having a total carbon number of 5 to 12 substituents and having a linear, branched, or alicyclic alkyl group as a substituent, and examples thereof include n-octylbenzene, n-nonylbenzene, n-decylbenzene, and dodecylbenzene.

[0055] The naphthalene derivative is not particularly limited, but alkyl-substituted naphthalene derivatives are preferred, and examples thereof include 1-methylnaphthalene, 2-ethylnaphthalene, 2-isopropylnaphthalene, 2,6-dimethylnaphthalene, and 1-methoxynaphthalene.

[0056] Examples of the hydronaphthalene derivatives include tetrahydronaphthalene, 1,2-dihydronaphthalene, and 1,4-dihydronaphthalene, and these may be substituted with an alkyl group having 1 to 6 carbon atoms.

[0057] The biphenyl derivative is not particularly limited, but is preferably a biphenyl derivative substituted with an alkyl group having 1 to 6 carbon atoms, and examples thereof include 3-ethylbiphenyl and 4-isopropylbiphenyl.

[0058] Other preferred aromatic hydrocarbon solvents include diphenylmethane and methyldiphenylmethane.

[0059] Examples of the aromatic ester solvent include benzoate solvents, phenylacetate solvents, and phthalate solvents.

[0060] Benzoate-based solvents are compounds having benzoic acid and an ester bond. Compounds formed by ester bonding of benzoic acid, which may have a substituent, and an alcohol having 2 to 12 carbon atoms can be used. The substituents that may be present are preferably linear or branched alkyl groups having 1 to 6 carbon atoms or linear or branched alkoxy groups having 1 to 6 carbon atoms. There may be multiple substituents, and in the case of multiple substituents, the total number of carbon atoms of the substituents is preferably 6 or less. Examples of benzoate-based solvents include butyl benzoate, n-pentyl benzoate, isoamyl benzoate, n-hexyl benzoate, 2-ethylhexyl benzoate, benzyl benzoate, and ethyl 4-methoxybenzoate.

[0061] Examples of the phenylacetate-based solvent include ethyl phenylacetate.

[0062] Examples of the phthalate-based solvents include dimethyl phthalate, diethyl phthalate, and dibutyl phthalate.

[0063] Other preferred aromatic ester solvents include 2-phenoxyethyl acetate and 2-phenoxyethyl isobutyrate.

[0064] The aromatic ether solvent is a compound having an aromatic ring and an ether bond, and examples thereof include the following aromatic ether solvents.

[0065] Examples of diphenyl ether derivatives that may be substituted with a linear or branched alkyl group having 1 to 6 carbon atoms include diphenyl ether, 2-phenoxytoluene, 3-phenoxytoluene, and 4-phenoxytoluene;

[0066] Examples of the benzene derivative having two ether bonds with a linear or branched alkyl group having 1 to 6 carbon atoms include 1,4-diethoxybenzene and 1-ethoxy-4-hexyloxybenzene;

[0067] Examples of the benzene derivative having one ether bond with a linear or branched alkyl group having 4 to 12 carbon atoms include phenylhexyl ether;

[0068] As the benzyl ether-based solvent, for example, dibenzyl ether;

[0069] Another aromatic ether solvent is 2-phenoxyethanol.

[0070] The aromatic ketone solvent is a compound having an aromatic ring and a ketone structure, and examples thereof include 1-acetylnaphthalene.

[0071] The solvent used in the present invention may be a water-insoluble non-aromatic solvent having a boiling point of 245° C. or higher. Examples of the water-insoluble non-aromatic solvent include ether solvents and glycol ester solvents.

[0072] Here, a water-insoluble aromatic solvent is used as the first solvent.

[0073] <Boiling Point>

[0074] The first solvent is a water-insoluble aromatic solvent having a boiling point 10° C. or higher than that of the second solvent having a boiling point of 245° C. or higher and a flow activation energy of 22 kJ / mol or higher and 35 kJ / mol or lower.

[0075] Among the solvents contained in the composition of the present invention, all water-insoluble aromatic solvents having a boiling point of 245° C. or higher and a flow activation energy of 22 kJ / mol or higher and 35 kJ / mol or lower correspond to the first solvent, and the first solvent refers to all solvents corresponding to the first solvent.

[0076] The boiling points of the first solvent and the second solvent used in the present invention are both above 245°C, and the boiling point of the first solvent is higher than that of the second solvent by more than 10°C. Therefore, during the drying process after coating, the second solvent with a lower boiling point usually evaporates before the first solvent. As described later, when a liquid film is formed by the composition sprayed into the barrier and the liquid film is dried by vacuum drying, the second solvent with a lower boiling point evaporates first. At this time, the temperature of the liquid film decreases due to the removal of the heat of vaporization. At this time, if the flow activation energy of the first solvent remaining in the liquid film is within the above range, the viscosity rises sharply, the flow rate of the liquid slows down, the shape of the film can be controlled, and a flat film can be obtained.

[0077] Among the solvents contained in the composition of the present invention, all solvents that satisfy all three conditions (a) to (c), namely, (a) a boiling point of 245° C. or higher, (b) a solvent other than the solvent equivalent to the first solvent, and (c) a solvent having a boiling point lower than the boiling point of all solvents equivalent to the first solvent, are solvents equivalent to the second solvent, and the second solvents are all solvents equivalent to the second solvent.

[0078] When the composition of the present invention contains multiple solvents corresponding to the first solvent, all of the multiple solvents corresponding to the first solvent are the first solvent, and the boiling point of the first solvent is the weighted average boiling point of all solvents corresponding to the first solvent. Similarly, when the composition of the present invention contains multiple solvents corresponding to the second solvent, all of the multiple solvents corresponding to the second solvent are the second solvent, and the boiling point of the second solvent is the weighted average boiling point of all solvents corresponding to the second solvent.

[0079] The weighted average boiling point is the sum of the values ​​obtained by multiplying the boiling points of the individual solvents by the weight ratio of the solvents. In the present invention, unless otherwise specified, the boiling point of the first solvent is the weighted average boiling point of all solvents equivalent to the first solvent, and the boiling point of the second solvent is the weighted average boiling point of all solvents equivalent to the second solvent.

[0080] The difference between the boiling points of the first solvent and the second solvent is 10°C or greater, preferably 15°C or greater, and more preferably 20°C or greater. A boiling point difference of 25°C or greater is more preferred because the second solvent tends to volatilize more significantly before the first solvent, and is more preferably 30°C or greater, and particularly preferably 35°C or greater. A boiling point difference of this value or greater is preferred because it facilitates adjustment of drying conditions, particularly vacuum drying conditions, during the drying process, particularly vacuum drying, so that the second solvent is first released in large quantities and then the first solvent is volatilized.

[0081] It is further preferred that, in addition to the above-mentioned boiling point difference, the difference between the boiling point of the solvent with the highest weight ratio when multiple solvents corresponding to the first solvent are included and the boiling point of the solvent with the highest weight ratio when multiple solvents corresponding to the second solvent are included is also 10°C or greater, preferably 15°C or greater, and even more preferably 20°C or greater. A boiling point difference of 25°C or greater is further preferred because the second solvent tends to volatilize more significantly before the first solvent, further preferably 30°C or greater, and particularly preferably 35°C or greater. The drying process tends to reflect the volatility of the solvent with the highest weight ratio, so the boiling point difference of the solvent with the highest weight ratio is preferably greater than the above-mentioned value.

[0082] From the perspective of facilitating solvent volatilization during the drying process, particularly from the perspective of facilitating solvent volatilization during vacuum drying, the boiling point of the first solvent is preferably 400°C or lower, and the boiling point of the second solvent is preferably 370°C or lower. Therefore, the upper limit of the boiling point difference between the first and second solvents is 155°C.

[0083] The second solvent may be a non-water-soluble aromatic solvent having a boiling point of 245°C or higher, or a non-water-soluble non-aromatic solvent having a boiling point of 245°C or higher. The second solvent is particularly preferably a non-water-soluble aromatic solvent having a boiling point of 245°C or higher. By having a boiling point of 245°C or higher, it is possible to prevent the solvent from vaporizing before the vacuum drying process, even at the end of the panel that dries quickly. Therefore, the temperature can be sufficiently lowered during the vacuum drying process, and a flat film can be obtained even at the end of the panel. The boiling point of the second solvent is preferably above 250°C, more preferably above 255°C, and most preferably above 260°C. The second solvent preferably evaporates earlier than the first solvent during the drying process, and therefore, the boiling point of the second solvent is preferably below 320°C, more preferably below 300°C, and particularly preferably below 280°C.

[0084] The number of the solvent equivalent to the first solvent contained in the first solvent, which accounts for the majority of the first solvent, i.e., 80% by weight or more of the first solvent, is preferably 5 or less, more preferably 3 or less, and particularly preferably 2 or less. When the number of the first solvent is within this range, management of the composition is facilitated. Furthermore, it is believed that the drying process of the first solvent is easily controlled, making it easier to obtain a flat film.

[0085] The number of the solvent equivalent to the second solvent contained in the second solvent, which constitutes the majority of the second solvent, i.e., 80% or more by weight of the second solvent, is preferably 5 or less, more preferably 3 or less, particularly preferably 2 or less, and most preferably 1 or less. When the number of the second solvent is within this range, management of the composition is facilitated. Furthermore, it is believed that when the number of the second solvent is within this range, control of the initial stage of the drying process is facilitated, allowing most of the second solvent to be volatilized in the initial drying stage, and controlling the temperature drop and viscosity increase of the first solvent due to the heat of vaporization.

[0086] In addition, in the present invention, the boiling point of the solvent is a value measured under atmospheric pressure.

[0087] <Flow Activation Energy>

[0088] The flow activation energy is E in the following formula (I). The flow activation energy is determined by measuring the viscosity of the solvent while changing the temperature, plotting the logarithm of the viscosity against the reciprocal of the temperature, and calculating the slope.

[0089] η=Aexp(E / RT) (I)

[0090] η: Viscosity (cP)

[0091] A: Constant

[0092] E: Flow activation energy (kJ / mol)

[0093] R: Gas constant (8.314 J / K / mol)

[0094] T: Temperature (K)

[0095] The flow activation energy of the first solvent is 22 kJ / mol or more and 35 kJ / mol or less. The lower limit of the flow activation energy of the first solvent is preferably 23 kJ / mol or more, more preferably 24 kJ / mol or more. The upper limit of the flow activation energy of the first solvent is preferably 34 kJ / mol or less, more preferably 32 kJ / mol or less, and even more preferably 30 kJ / mol or less.

[0096] If the flow activation energy of the first solvent is above the lower limit, the viscosity increases moderately quickly when the temperature decreases, making it easier to control the flatness of the functional film. If the flow activation energy of the first solvent is below the upper limit, the rate of viscosity increase when the temperature decreases does not increase too quickly and the ultimate viscosity does not become too high, making it easier to control the flatness of the functional film, which is preferred.

[0097] The flow activation energy of the first solvent is preferably greater than the flow activation energy of the second solvent by 5 kJ / mol or more. In other words, the flow activation energy of the second solvent is preferably lower than the flow activation energy of the first solvent by 5 kJ / mol or more. By falling within this range, the interaction between the flow activation energy of the first solvent and the second solvent is clarified, making design easier.

[0098] When the composition is applied inside the dike and dried to form a film, if the amount of liquid in the dike is relatively large and the amount of liquid gradually decreases while the solvent evaporates, even if the heat of vaporization is taken away and the liquid temperature decreases, the second solvent with low flow activation energy also exists to some extent. Therefore, it is not easy to thicken and the fluidity of the liquid is maintained. During the drying process such as vacuum drying, if the liquid level drops while the solvent evaporates inside the dike, the fluidity of the liquid is maintained, then with the drop of the liquid level, the liquid on the side of the dike also wets and drops, and the liquid is not easy to remain on the side of the dike. As a result, it is believed that it is easy to make the film thickness of the edge of the dike uniform. On the contrary, if the difference in flow activation energy between the first solvent and the second solvent is small, sometimes even if the second solvent remains to some extent, it is cooled and thickened due to the heat of vaporization. In the present invention, the increase in viscosity is preferably within an appropriate range. Therefore, by making one solvent a solvent that is not easy to thicken and the other solvent a solvent that is easy to thicken, the optimal thickening state can be easily selected according to the film thickness, material, drying distribution, etc. Therefore, it is preferable to set a difference in flow activation energy between the first solvent and the second solvent as described above.

[0099] From the perspective that the composition maintains fluidity and easily reduces the wetting of the side of the partition in the initial stage of drying, the difference in flow activation energy between the first solvent and the second solvent is particularly preferably 5.2 kJ / mol or more, especially preferably 5.5 kJ / mol or more, preferably 21.0 kJ / mol or less, and especially preferably 20.0 kJ / mol or less.

[0100] Examples of water-insoluble aromatic solvents suitable as the first solvent and having a flow activation energy of 22 kJ / mol or more and 35 kJ / mol or less include 2-ethylhexyl benzoate (23.4 kJ / mol), benzyl benzoate (24.5 kJ / mol), diethyl phthalate (27.5 kJ / mol), 2-phenoxyethyl acetate (28.6 kJ / mol), and isopropylbiphenyl (24.0 kJ / mol).

[0101] Examples of the second solvent having a flow activation energy 5 kJ / mol or more smaller than that of the first solvent include dibenzyl ether (18.7 kJ / mol), 3-phenoxytoluene (20.1 kJ / mol), and diphenyl ether (18.3 kJ / mol).

[0102] <Viscosity>

[0103] The second solvent preferably has a viscosity of 5 mPas or less at 23°C. By keeping the viscosity of the second solvent below the upper limit, it is possible to select a first solvent with a slightly higher viscosity or a functional material that easily increases viscosity when preparing the composition, thereby broadening the selection range of the first solvent or functional material and the ink concentration.

[0104] The viscosity of the second solvent is particularly preferably 4.5 mPas or less. On the other hand, from the viewpoint of easily retaining the ink in the inkjet head when filled in the inkjet head, the viscosity of the second solvent is preferably 1.0 mPas or more.

[0105] In the present invention, the viscosity of the solvent can be measured using an E-type viscometer RE85L (manufactured by Toki Sangyo) at 23° C. and a cone and plate rotation speed of 20 to 100 rpm.

[0106] The viscosity of the first solvent is preferably 3 mPas or more and 20 mPas or less.

[0107] <Surface Tension>

[0108] The surface tension of the first solvent is preferably more than 30mN / m, preferably less than 45mN / m. It is believed that the surface tension of the first solvent is within this range, and the surface tension of the ink as a whole is maintained within an appropriate range, so that the inkjet device can be utilized to stably eject. In addition, it is believed that the surface tension of the first solvent is within this range, and the liquid level in the dike is easily flattened, which is preferred. The surface tension of the first solvent is above the above lower limit, and a certain tension is generated on the liquid surface during drying, and the surface area is desired to become smaller, so it is difficult to produce wrinkles on the film. On the other hand, the surface tension of the first solvent is below the above upper limit, and it is difficult to produce a surface tension difference during drying, and it is difficult to produce useless Marangoni convection, etc., so it is easy to form a flat film, which is preferred.

[0109] In the present invention, the surface tension of the solvent can be measured by a plate method using a platinum plate at 23.0°C.

[0110] <Solvent Combination>

[0111] The first solvent and the second solvent contained in the composition of the present invention may each be one kind or two or more kinds.

[0112] In particular, by including two or more first solvents, the surface tension that facilitates convection of the solvents can be adjusted, thereby further improving the flatness, which is preferred.

[0113] The first solvent and the second solvent contained in the composition of the present invention are preferably both water-insoluble solvents, and more preferably both the first solvent and the second solvent are water-insoluble aromatic solvents.

[0114] In particular, from the viewpoint that the functional material dissolves well and does not easily precipitate even in the drying step, the first solvent and the second solvent are each preferably any one of naphthalene, benzoic acid ester, and aromatic ether which may have a substituent.

[0115] Among the above-mentioned solvents, preferred combinations of the first solvent and the second solvent include the following combinations.

[0116] The first solvent is preferably at least any one of 2-ethylhexyl benzoate, benzyl benzoate, 1-acetylnaphthalene, dimethyl phthalate, diethyl phthalate, ethylbiphenyl, isopropylbiphenyl, diisopropylbiphenyl, triisopropylbiphenyl, and 2-phenoxyethyl isobutyrate, and more preferably one or more of 2-ethylhexyl benzoate, benzyl benzoate, 1-acetylnaphthalene, dimethyl phthalate, and 2-phenoxyethyl isobutyrate.

[0117] The second solvent is preferably any one of methylnaphthalene, ethylnaphthalene, isopropylnaphthalene, methoxynaphthalene, butyl benzoate, amyl benzoate, isoamyl benzoate, diphenylmethane, and benzyltoluene, and more preferably one or more of methylnaphthalene, ethylnaphthalene, and butyl benzoate.

[0118] Furthermore, preferred combinations of the first solvent and the second solvent mainly include combinations of 2-ethylhexyl benzoate and methylnaphthalene, 2-ethylhexyl benzoate and ethylnaphthalene, 2-ethylhexyl benzoate and isopropylnaphthalene, 2-ethylhexyl benzoate and butyl benzoate, 2-ethylhexyl benzoate and isoamyl benzoate, benzyl benzoate and methylnaphthalene, benzyl benzoate and ethylnaphthalene, benzyl benzoate and isopropylnaphthalene, benzyl benzoate and butyl benzoate, and benzyl benzoate and isoamyl benzoate.

[0119] When the composition of the present invention contains two or more first solvents, preferred combinations thereof include, for example, combinations of 2-ethylhexyl benzoate and benzyl benzoate, 2-ethylhexyl benzoate and dimethyl phthalate, and 2-ethylhexyl benzoate and 1-acetylnaphthalene.

[0120] [Contents of the first solvent and the second solvent]

[0121] The first solvent content is 5 to 50% by weight relative to the total amount of solvent in the composition of the present invention. To effectively lower the temperature of the first solvent through volatilization of the second solvent, it is necessary to increase the volatile components. Therefore, the first solvent content is 50% by weight or less, preferably 40% by weight or less, and more preferably 30% by weight or less. To dissolve the functional material during volatilization of the second solvent, the first solvent content is 5% by weight or more, preferably 10% by weight or more, and more preferably 15% by weight or more.

[0122] The total content of the first and second solvents relative to the total amount of solvents contained in the composition is preferably 50% by weight or more, more preferably 70% by weight or more, further preferably 80% by weight or more, particularly preferably 85% by weight or more, especially preferably 90% by weight or more, and most preferably 95% by weight or more, with an upper limit of 100% by weight. When the total content of the first and second solvents is above the above lower limit, the composition can be used as an ink ejectable from a micro nozzle, the drying of the solvent can be easily controlled, and the effects of the present invention can be easily achieved.

[0123] <Other solvents>

[0124] The composition of the present invention may contain a solvent other than the first solvent and the second solvent.

[0125] As solvents other than the first and second solvents, one or more solvents having a boiling point lower than 245° C. may be used, such as dibenzyl ether or benzyltoluene, which are high-boiling-point components having low flow activation energy.

[0126] By including these other solvents, there is an advantage in that the thickening effect accompanying the temperature drop can be adjusted by the material. However, in order to reliably obtain the effect of the present invention brought about by including the first solvent and the second solvent, the content of the other solvents other than the first solvent and the second solvent is preferably 50% by weight or less, more preferably 30% by weight or less, further preferably 20% by weight or less, particularly preferably 15% by weight or less, especially preferably 10% by weight or less, and most preferably 5% by weight or less, relative to the total solvent contained in the composition of the present invention.

[0127] [Functional Materials]

[0128] The functional material in the present invention preferably has a molecular weight of 50,000 or less. The functional material in the present invention can be a low-molecular-weight material or a high-molecular-weight material. In the case of a low-molecular-weight material, a more significant effect can be obtained. Here, the low-molecular-weight material preferably has a molecular weight of 10,000 or less, more preferably a molecular weight of 5,000 or less.

[0129] As the functional material in the present invention, the light-emitting layer material, hole injection layer material, hole transport layer material or electron transport layer material described later can be used, preferably the light-emitting layer material, hole injection layer material or hole transport layer material, and particularly preferably a low-molecular-weight light-emitting layer material.

[0130] The composition of the present invention may contain only one functional material or two or more functional materials.

[0131] [Content of solvent and functional material]

[0132] The content of the functional material in the composition of the present invention is not particularly limited, but is preferably 0.1 wt % or more, more preferably 0.5 wt % or more, more preferably 1.0 wt % or more, and preferably 20 wt % or less, more preferably 15 wt % or less, and more preferably 10 wt % or less.

[0133] Specific examples of the composition of the present invention include the luminescent layer-forming composition, hole injection layer-forming composition, hole transport layer-forming composition, and electron transport layer-forming composition described below. The preferred content of the solvent in each layer-forming composition is described below. Furthermore, the content of the functional material in each layer-forming composition also corresponds to the content of the luminescent layer material, hole injection layer material, hole transport layer material, and electron transport layer material described below.

[0134] [Film formation using a wet film forming method]

[0135] The composition of the present invention is suitable for forming a functional film in the production of an organic electroluminescent element. The structure of the organic electroluminescent element will be described below.

[0136] The organic electroluminescent element of the present invention typically has microscopic regions of light-emitting pixels divided by partitions called banks on a substrate provided with electrodes. A functional film is formed by spraying the composition of the present invention onto the microscopic regions divided by the banks, drying the film, and then heating the film as appropriate.

[0137] The ejection method is a method of ejecting droplets smaller than the micro-areas divided by the banks from a micro-nozzle, preferably ejecting a plurality of droplets so that the micro-areas divided by the banks are filled with the composition of the present invention.

[0138] In the wet film-forming method, after the microscopic regions defined by the dikes are filled with the composition of the present invention, vacuum drying is performed. Vacuum drying volatilizes the solvent by reducing pressure. In the present invention, since the first solvent has a higher boiling point than the second solvent, the second solvent generally has a higher vapor pressure and volatilizes before the first solvent. When the second solvent volatilizes, the heat of vaporization is dissipated, and the temperature of the composition within the dikes gradually decreases. The second solvent preferably does not increase viscosity much due to the decrease in temperature. Therefore, as mentioned above, the flow activation energy of the second solvent is preferably lower than that of the first solvent. Thus, while a certain amount of the second solvent remains, the viscosity does not increase much. However, if most of the second solvent evaporates, the temperature of the composition drops further, and the viscosity of the composition increases sharply due to the remaining first solvent with a higher flow activation energy, making it difficult for the liquid to flow. Therefore, within the composition within the microscopic regions defined by the dikes, liquid migration due to concentration gradients or Marangoni convection is less likely to occur. This can suppress the disturbance of the liquid surface shape due to the flow of the composition during the solvent volatilization process, and can control the drying conditions so that the surface of the dried film after the solvent volatilization becomes uniform.

[0139] The first solvent and the second solvent can be largely volatilized by vacuum drying, but in order to fully volatilize them, they are then heated and dried. The heating temperature and time are preferably such that the functional film does not crystallize or aggregate.

[0140] When the functional material is a low molecular weight material, the heating temperature is usually 50°C or higher, preferably 80°C or higher, more preferably 100°C or higher, and more preferably 120°C or higher, and usually 200°C or lower, preferably 180°C or lower, and more preferably 150°C or lower. The heating time is usually 1 minute or longer, preferably 3 minutes or longer, more preferably 5 minutes or longer, and usually 120 minutes or shorter, preferably 90 minutes or shorter, and more preferably 60 minutes or shorter.

[0141] When the functional material is a polymer material, the heating temperature is usually 80°C or higher, preferably 100°C or higher, more preferably 150°C or higher, and more preferably 200°C or higher, and usually 300°C or lower, preferably 270°C or lower, and more preferably 240°C or lower. The heating time is usually 1 minute or longer, preferably 3 minutes or longer, more preferably 5 minutes or longer, and usually 120 minutes or shorter, preferably 90 minutes or shorter, and more preferably 60 minutes or shorter.

[0142] Heating methods can be implemented using a hot plate, oven, infrared irradiation, or the like. For infrared irradiation, which directly imparts molecular vibrations, a heating time close to the aforementioned lower limit is sufficient. However, when heating with a hot plate, where the substrate is in direct contact with the heat source or the heat source is placed very close to the substrate, a longer heating time is required. In oven heating, utilizing the gas within the oven (typically air or an inert gas such as nitrogen or argon), the temperature rise takes time, so a heating time close to the aforementioned upper limit is preferred. The heating time can be adjusted appropriately depending on the heating method.

[0143] [Functional membrane]

[0144] The functional material contained in the functional film is generally 70% by weight or more, preferably 80% by weight or more, more preferably 90% by weight or more, particularly preferably 95% by weight or more, and most preferably substantially 100% by weight, with an upper limit of 100% by weight. Substantially 100% by weight means that the functional film may contain trace amounts of additives, residual solvents, and impurities. By keeping the content of the functional material in the functional film within this range, the functions of the functional material can be more effectively demonstrated.

[0145] [Layer Structure and Formation Method of Organic Electroluminescent Element]

[0146] Reference Figure 1 Preferred examples of embodiments of the layer structure of an organic electroluminescent element produced using the composition of the present invention (hereinafter sometimes referred to as “the organic electroluminescent element of the present invention”) and a method for forming the same will be described.

[0147] Figure 1 Schematic diagram showing a cross section of a structural example of an organic electroluminescent element 10 of the present invention. Figure 1 1 represents a substrate, 2 represents an anode, 3 represents a hole injection layer, 4 represents a hole transport layer, 5 represents a light-emitting layer, 6 represents a hole blocking layer, 7 represents an electron transport layer, 8 represents an electron injection layer, and 9 represents a cathode.

[0148] The organic electroluminescent element of the present invention has an anode, a light-emitting layer and a cathode as essential constituent layers, but may also have a plurality of layers as required. Figure 1 It is shown that further functional layers are present between the anode 2 and the light-emitting layer 5 and between the cathode 9 and the light-emitting layer 5 .

[0149] [Substrate]

[0150] Substrate 1 serves as a support for the organic electroluminescent element. For substrate 1, materials such as quartz or glass plates, metal plates or foils, and plastic films or sheets can be used. Glass plates are particularly preferred, as are plates made of transparent synthetic resins such as polyester, polymethacrylate, polycarbonate, and polysulfone. When using a synthetic resin substrate, it is preferable to pay attention to its gas barrier properties. Since the organic electroluminescent element is less susceptible to degradation due to external air passing through the substrate, the substrate preferably has high gas barrier properties. Therefore, one preferred method is to ensure gas barrier properties by, for example, providing a dense silicon oxide film on at least one surface of the synthetic resin substrate.

[0151] [anode]

[0152] The anode 2 is an electrode that plays a role in injecting holes into the layer on the light-emitting layer 5 side.

[0153] The anode 2 is generally composed of metals such as aluminum, gold, silver, nickel, palladium, and platinum, metal oxides such as indium and / or tin oxides, metal halides such as copper iodide, carbon black, or conductive polymers such as poly(3-methylthiophene), polypyrrole, and polyaniline.

[0154] The anode 2 is usually formed by a method such as sputtering or vacuum deposition.

[0155] When the anode 2 is formed using metal particles such as silver, copper iodide, carbon black, conductive metal oxide particles, conductive polymer fine powder, etc., the anode 2 can also be formed by dispersing these particles in an appropriate binder resin solution and applying it on the substrate 1.

[0156] In the case of a conductive polymer, a thin film can also be formed directly on the substrate 1 by electrolytic polymerization.

[0157] Alternatively, the anode 2 may be formed by coating a conductive polymer on the substrate 1 (Appl. Phys. Lett., Vol. 60, p. 2711, 1992).

[0158] The anode 2 generally has a single-layer structure, but may also have a laminated structure composed of a plurality of materials as desired.

[0159] The thickness of the anode 2 can be appropriately selected based on the desired transparency, etc. When transparency is required, the transmittance of visible light is generally 60% or greater, preferably 80% or greater. In this case, the thickness of the anode 2 is generally 5 nm or greater, preferably 10 nm or greater, and generally 1000 nm or less, preferably approximately 500 nm or less. When opacity is desired, the thickness of the anode 2 is arbitrary. A substrate 1 that also functions as the anode 2 may also be used. Different conductive materials may also be laminated on the anode 2.

[0160] In order to remove impurities adhering to the anode 2 and adjust the ionization potential to improve the hole injection property, the surface of the anode 2 is preferably subjected to ultraviolet (UV) / ozone treatment or oxygen plasma or argon plasma treatment.

[0161] [Hole injection layer]

[0162] The hole injection layer 3 is a layer that transports holes from the anode 2 to the light-emitting layer 5. When the hole injection layer 3 is provided, the hole injection layer 3 is usually formed on the anode 2.

[0163] The hole injection layer 3 may be formed by vacuum deposition or wet film formation, and is not particularly limited. From the perspective of reducing dark spots, the hole injection layer 3 is preferably formed by wet film formation.

[0164] The thickness of the hole injection layer 3 is usually 5 nm or more, preferably 10 nm or more, and usually 1000 nm or less, preferably 500 nm or less.

[0165] (Hole Transport Material)

[0166] The hole injection layer-forming composition generally contains a hole transport material and a solvent as constituent materials of the hole injection layer 3 .

[0167] The hole transport material may be a high molecular weight compound such as a polymer or a low molecular weight compound such as a monomer, as long as it is a compound having hole transport properties generally used in the hole injection layer 3 of an organic electroluminescent element, but is preferably a high molecular weight compound.

[0168] As the hole transport material, a compound having an ionization potential of 4.5 eV to 6.0 eV is preferred from the viewpoint of the barrier for charge injection from the anode 2 to the hole injection layer 3. Examples of the hole transport material include aromatic amine derivatives, phthalocyanine derivatives, porphyrin derivatives, oligothiophene derivatives, polythiophene derivatives, benzylphenyl derivatives, compounds in which a tertiary amine is linked to a fluorenyl group, hydrazone derivatives, silazane derivatives, silylamine derivatives, phosphineamine derivatives, quinacridone derivatives, polyaniline derivatives, polypyrrole derivatives, polyphenylene vinylene derivatives, polythiophene vinylene derivatives, polyquinoline derivatives, polyquinoxaline derivatives, and carbon.

[0169] In the present invention, the derivatives, for example, aromatic amine derivatives, include aromatic amine itself and compounds with aromatic amine as the main skeleton, and may be polymers or monomers.

[0170] The hole transport material used as the material for the hole injection layer 3 may contain any one of these compounds alone or two or more thereof. When two or more hole transport materials are contained, their combination is arbitrary, but it is preferred to use one or two or more aromatic tertiary amine polymer compounds in combination with one or two or more other hole transport materials.

[0171] As hole transport materials, aromatic amine compounds are preferred among the above examples from the perspective of amorphousness and visible light transmittance, and aromatic tertiary amine compounds are particularly preferred. Aromatic tertiary amine compounds also include compounds having an aromatic tertiary amine structure, that is, compounds having a group derived from an aromatic tertiary amine.

[0172] The type of aromatic tertiary amine compound is not particularly limited. However, from the perspective of uniform luminescence due to the surface smoothing effect, a polymer compound (a polymeric compound in which repeating units are linked) having a weight average molecular weight of 1,000 to 1,000,000 is more preferred. Preferred examples of aromatic tertiary amine polymer compounds include polymer compounds having repeating units represented by the following formula (1) or the following formula (11).

[0173]

[0174] (In formula (1),

[0175] Ar 3 represents an aromatic hydrocarbon group or aromatic heterocyclic group which may have a substituent,

[0176] Ar 4 represents a divalent aromatic hydrocarbon group or a divalent aromatic heterocyclic group which may have a substituent, or a divalent group in which a plurality of aromatic hydrocarbon groups and aromatic heterocyclic groups are linked directly or via a linking group)

[0177] In the above formula (1), when a plurality of aromatic hydrocarbon groups and aromatic heterocyclic groups are connected via a connecting group, the connecting group is a divalent connecting group, and examples thereof include a group in which 1 to 30 groups selected from -O- group, -C(=O)- group and (which may have a substituent) -CH2- group are connected in any order, preferably 1 to 5, and more preferably 1 to 3.

[0178] Among the linking groups, Ar in formula (1) is preferred from the viewpoint of excellent hole injection into the light-emitting layer. 4 It is a plurality of aromatic hydrocarbon groups or aromatic heterocyclic groups connected via a linking group represented by the following formula (2).

[0179]

[0180] (In formula (2),

[0181] d represents an integer from 1 to 10,

[0182] R 8 and R 9 Each independently represents a hydrogen atom or an alkyl group, an aromatic hydrocarbon group or an aromatic heterocyclic group which may have a substituent;

[0183] R 8 、R 9 When there are multiple, they may be the same or different)

[0184]

[0185] In the above formula (11), j, k, l, m, n, and p each independently represent an integer greater than or equal to 0. Wherein, l+m≥1. 11 、Ar 12 、Ar 14 Each independently represents a divalent aromatic ring group having 30 or less carbon atoms which may have a substituent. 13 represents a divalent aromatic ring group having 30 or less carbon atoms which may have a substituent, or a divalent group represented by the following formula (12), Q 11 , Q 12 Each independently represents an oxygen atom, a sulfur atom, a hydrocarbon chain having 6 or less carbon atoms which may have a substituent, S 1 ~S 4 Each is independently represented by a group represented by the following formula (13).

[0186] In addition, the aromatic ring group mentioned here refers to an aromatic hydrocarbon ring group and an aromatic heterocyclic group.

[0187] As Ar 11 、Ar 12 、Ar 14 Examples of the aromatic ring group include a monocyclic ring, 2 to 6 condensed rings, or a group in which two or more of these aromatic rings are connected. Specific examples of the monocyclic or 2 to 6 condensed ring aromatic ring group include rings derived from benzene, naphthalene, anthracene, phenanthrene, perylene, tetracene, pyrene, benzopyrene, Ring, triphenylene ring, acenaphthene ring, fluoranthene ring, fluorene ring, biphenyl, terphenyl, quaterphenyl, furan ring, benzofuran ring, thiophene ring, benzothiophene ring, pyrrole ring, pyrazole ring, imidazole ring, oxadiazole ring, indole ring, carbazole ring, pyrroloimidazole ring, pyrrolopyrazole ring, pyrrolopyrrole ring, thienopyrrole ring, thienothiophene ring, furopyrrole ring, furofuran ring, thienofuran ring, benzisothiazolyl ring A divalent group derived from an oxazole ring, a benzisothiazole ring, a benzimidazole ring, a pyridine ring, a pyrazine ring, a pyridazine ring, a pyrimidine ring, a triazine ring, a quinoline ring, an isoquinoline ring, a cinnoline ring, a quinoxaline ring, a phenanthridine ring, a benzimidazole ring, a phenanthridine ring, a quinazoline ring, a quinazolinone ring, or an azulene ring. Among them, a divalent group derived from a benzene ring, a naphthalene ring, a fluorene ring, a pyridine ring, or a carbazole ring, or a biphenyl group is preferred from the perspectives of efficient delocalization of negative charge, excellent stability, and excellent heat resistance.

[0188] As Ar 13 Examples of aromatic ring groups, with Ar 11 、Ar 12 、Ar 14 The same situation.

[0189]

[0190] In the above formula (12), R 11 represents an alkyl group, an aromatic ring group, or a trivalent group consisting of an alkyl group having 40 or less carbon atoms and an aromatic ring group, which may have a substituent. 12 represents an alkyl group, an aromatic ring group, or a divalent group consisting of an alkyl group having 40 or less carbon atoms and an aromatic ring group, which may have a substituent. 31 represents a monovalent aromatic ring group or a monovalent crosslinking group, which may have a substituent. q represents 1 to 4. When q is 2 or more, multiple R 12 Can be the same or different, multiple Ar 31 They may be the same or different. The asterisk (*) indicates the bonding site to the nitrogen atom of formula (11).

[0191] As R 11 The aromatic ring group is preferably an aromatic ring group which is a monocyclic or condensed ring having 3 to 30 carbon atoms or a group formed by linking 2 to 6 of them. Specific examples include trivalent groups derived from a benzene ring, a fluorene ring, a naphthalene ring, a carbazole ring, a dibenzofuran ring, a dibenzothiophene ring, and a group formed by linking 2 to 6 of them.

[0192] As R 11 The alkyl group preferably includes a linear, branched or cyclic alkyl group having 1 to 12 carbon atoms, and specific examples thereof include groups derived from methane, ethane, propane, isopropane, butane, isobutane, pentane, hexane, and octane.

[0193] As R 11 The group composed of an alkyl group having 40 or less carbon atoms and an aromatic ring group is preferably a group formed by connecting a linear, branched or cyclic alkyl group having 1 to 12 carbon atoms and an aromatic ring group which is a monocyclic or condensed ring having 3 to 30 carbon atoms or a group formed by connecting 2 to 6 aromatic ring groups.

[0194] As R 12 Specific examples of the aromatic ring group include divalent groups derived from a benzene ring, a fluorene ring, a naphthalene ring, a carbazole ring, a dibenzofuran ring, a dibenzothiophene ring, and a linked ring having 30 or less carbon atoms formed by linking these rings.

[0195] As R 12 Specific examples of the alkyl group include divalent groups derived from methane, ethane, propane, isopropane, butane, isobutane, pentane, hexane, and octane.

[0196] As Ar 31 Specific examples of the aromatic ring group include monovalent groups derived from a benzene ring, a fluorene ring, a naphthalene ring, a carbazole ring, a dibenzofuran ring, a dibenzothiophene ring, and a linked ring having 30 or less carbon atoms formed by linking these rings.

[0197] As an example of a preferred structure of formula (12), the following structure can be cited: R 11 The partial structure of , that is, the benzene ring or fluorene ring of the main chain in the following structure may further have a substituent.

[0198]

[0199] As Ar 31 Examples of the crosslinking group include a group derived from a benzocyclobutene ring, a naphthocyclobutene ring or an oxetane ring, a vinyl group, an acryloyl group, etc. From the perspective of compound stability, a group derived from a benzocyclobutene ring or a naphthocyclobutene ring is preferred.

[0200]

[0201] In the above formula (13), x and y represent integers greater than or equal to 0. 21 、Ar 23 Each independently represents a divalent aromatic ring group, and these groups may have a substituent. 22 represents a monovalent aromatic ring group which may have a substituent, R 13 represents an alkyl group, an aromatic ring group, or a divalent group consisting of an alkyl group and an aromatic ring group, which may have a substituent. 32 represents a monovalent aromatic ring group or a monovalent crosslinking group, and these groups may have a substituent. The asterisk (*) represents a bonding site to the nitrogen atom in formula (11).

[0202] As Ar 21 、Ar 23 Examples of aromatic ring groups, with Ar 11 、Ar 12 、Ar 14 The same situation.

[0203] As Ar 22 、Ar 32 Examples of aromatic ring groups include single rings, 2 to 6 condensed rings, or groups formed by linking two or more of these aromatic rings. Specific examples include rings derived from benzene, naphthalene, anthracene, phenanthrene, perylene, tetracene, pyrene, benzopyrene, Ring, triphenylene ring, acenaphthene ring, fluoranthene ring, fluorene ring, biphenyl, terphenyl, quaterphenyl, furan ring, benzofuran ring, thiophene ring, benzothiophene ring, pyrrole ring, pyrazole ring, imidazole ring, oxadiazole ring, indole ring, carbazole ring, pyrroloimidazole ring, pyrrolopyrazole ring, pyrrolopyrrole ring, thienopyrrole ring, thienothiophene ring, furopyrrole ring, furofuran ring, thienofuran ring, benzisothiazolyl ring A monovalent group derived from an oxazole ring, a benzisothiazole ring, a benzimidazole ring, a pyridine ring, a pyrazine ring, a pyridazine ring, a pyrimidine ring, a triazine ring, a quinoline ring, an isoquinoline ring, a cinnoline ring, a quinoxaline ring, a phenanthridine ring, a benzimidazole ring, a quinazoline ring, a quinazolinone ring, or an azulene ring. Among them, a monovalent group derived from a benzene ring, a naphthalene ring, a fluorene ring, a pyridine ring, or a carbazole ring, or a biphenyl group is preferred from the perspectives of efficient delocalization of negative charge, excellent stability, and excellent heat resistance.

[0204] As R 13 Examples of alkyl or aromatic ring groups, with R 12 same.

[0205] Ar 32 The crosslinking group is not particularly limited, but preferred examples include a group derived from a benzocyclobutene ring, a naphthocyclobutene ring, or an oxetane ring, a vinyl group, an acryloyl group, and the like.

[0206] The above Ar 11 ~Ar 14 、R 11 ~R 13 、Ar 21 ~Ar 23 、Ar 31 ~Ar 32 , Q 11 , Q 12 As long as it does not violate the main purpose of the present invention, it may further have a substituent. The molecular weight of the substituent is preferably 400 or less, more preferably 250 or less. The type of substituent is not particularly limited, and as an example, one or more types selected from the following substituent group W can be cited.

[0207] [Substituent Group W]

[0208] an alkyl group having 1 or more carbon atoms, preferably 10 or less, and more preferably 8 or less, such as a methyl group and an ethyl group; an alkenyl group having 2 or more carbon atoms, preferably 11 or less, and more preferably 5 or less, such as a vinyl group; an alkynyl group having 2 or more carbon atoms, preferably 11 or less, and more preferably 5 or less, such as an ethynyl group; an alkoxy group having 1 or more carbon atoms, preferably 10 or less, and more preferably 6 or less, such as a methoxy group and an ethoxy group; an aryloxy group having 4 or more carbon atoms, preferably 5 or more and preferably 25 or less, and more preferably 14 or less, such as a phenoxy group, a naphthoxy group, and a pyridyloxy group; a methoxy group an alkoxycarbonyl group having 2 or more carbon atoms, preferably 11 or less, and more preferably 7 or less, such as a carbonyl group and an ethoxycarbonyl group; a dialkylamino group having 2 or more carbon atoms, preferably 20 or less, and more preferably 12 or less, such as a dimethylamino group and a diethylamino group; a diarylamino group having 10 or more carbon atoms, preferably 12 or more and 30 or less, and more preferably 22 or less, such as a diphenylamino group, a ditolylamino group, and an N-carbazolyl group; an arylalkyl group having 6 or more carbon atoms, more preferably 7 or more carbon atoms, and preferably 25 or less, and more preferably 17 or less carbon atoms, such as a phenylmethylamino group amino; acyl groups having 2 or more and preferably 10 or less, more preferably 7 or less carbon atoms, such as acetyl and benzoyl; halogen atoms such as fluorine and chlorine; haloalkyl groups having 1 or more and preferably 8 or less carbon atoms, more preferably 4 or less carbon atoms, such as trifluoromethyl; alkylthio groups having 1 or more and preferably 10 or less carbon atoms, more preferably 6 or less carbon atoms, such as methylthio and ethylthio; arylthio groups having 4 or more and preferably 5 or more and preferably 25 or less carbon atoms, more preferably 14 or less carbon atoms, such as phenylthio, naphthylthio and pyridylthio; trimethylsilyl, tris(2-methyl-4-thio)-1,2-dimethyl-1,3-dimethyl-1,4 ... Silyl groups having 2 or more, preferably 3 or more and preferably 33 or less, more preferably 26 or less carbon atoms, such as phenylsilyl; siloxy groups having 2 or more, preferably 3 or more and preferably 33 or less, more preferably 26 or less carbon atoms, such as trimethylsiloxy and triphenylsiloxy; cyano groups; aromatic hydrocarbon groups having 6 or more and preferably 30 or less, more preferably 18 or less carbon atoms, such as phenyl and naphthyl; aromatic heterocyclic groups having 3 or more, preferably 4 or more and preferably 28 or less, more preferably 17 or less carbon atoms, such as thienyl and pyridyl.

[0209] Among the above-mentioned substituent group W, an alkyl group or an alkoxy group is preferred from the viewpoint of improving solubility, and an aromatic hydrocarbon group or an aromatic heterocyclic group is preferred from the viewpoint of charge transportability and stability.

[0210] Among the polymer compounds having a repeating unit represented by the formula (11), polymer compounds having a repeating unit represented by the following formula (14) are particularly preferred because they have very high hole injection and transport properties.

[0211]

[0212] In the above formula (14), R 21 ~R 25 Each independently represents an arbitrary substituent. 21 ~R 25 Specific examples of the substituent are the same as the substituents described in the above-mentioned [Substituent Group W].

[0213] s and t each independently represent an integer of 0 or more and 5 or less.

[0214] u, v, and w each independently represent an integer of 0 or more and 4 or less.

[0215] Preferred examples of the aromatic tertiary amine polymer compound include polymer compounds containing repeating units represented by the following formula (15) and / or formula (16).

[0216]

[0217] In the above formula (15) and formula (16), Ar 45 、Ar 47 and Ar 48 Each independently represents a monovalent aromatic hydrocarbon group which may have a substituent or a monovalent aromatic heterocyclic group which may have a substituent. 44 and Ar 46 Each independently represents a divalent aromatic hydrocarbon group which may have a substituent or a divalent aromatic heterocyclic group which may have a substituent. 41 ~R 43 Each independently represents a hydrogen atom or an arbitrary substituent.

[0218] Ar 45 、Ar 47 and Ar 48 Specific examples, preferred examples, examples of substituents that may be possessed and preferred examples of substituents are the same as Ar 22 Likewise, Ar 44 and Ar 46 Specific examples, preferred examples, examples of substituents that may be possessed and preferred examples of substituents are the same as Ar 11 、Ar 12 and Ar 14 Likewise. As R 41 ~R 43 , preferably a hydrogen atom or a substituent described in the above-mentioned [Substituent Group W], more preferably a hydrogen atom, an alkyl group, an alkoxy group, an amino group, an aromatic hydrocarbon group or an aromatic heterocyclic group.

[0219] Preferred specific examples of the repeating units represented by formula (15) and formula (16) applicable to the present invention are given below, but the present invention is not limited to these.

[0220]

[0221] (Electron-accepting compound)

[0222] The hole injection layer-forming composition preferably contains an electron-accepting compound as a constituent material of the hole injection layer 3 .

[0223] The electron-accepting compound preferably has oxidizing power and the ability to accept one electron from the hole transport material. Specifically, the electron-accepting compound preferably has an electron affinity of 4.0 eV or higher, more preferably 5.0 eV or higher.

[0224] Examples of such electron-accepting compounds include triarylboron compounds, metal halides, Lewis acids, organic acids, More specifically, examples of the electron-accepting compound include 4-isopropyl-4'-methyldiphenyl iodide and 4-isopropyl-4'-methyldiphenyl iodide. Tetrakis(pentafluorophenyl)borate, triphenylsulfonium tetrafluoroborate, etc. substituted with organic groups Salts (International Publication No. 2005 / 089024, International Publication No. 2017 / 164268); high-valence inorganic compounds such as iron (III) chloride (Japanese Patent Publication No. 11-251067), ammonium peroxydisulfate, etc.; cyano compounds such as tetracyanoethylene, aromatic boron compounds such as tris(pentafluorophenyl)borane (Japanese Patent Publication No. 2003-31365); fullerene derivatives; iodine; sulfonate ions such as polystyrene sulfonate ion, alkylbenzene sulfonate ion, camphor sulfonate ion, etc.

[0225] The electron-accepting compound can improve the conductivity of the hole injection layer 3 by oxidizing the hole transport material.

[0226] (Other constituent materials)

[0227] The material of the hole injection layer 3 may further contain other components in addition to the hole transport material and the electron accepting compound as long as the effects of the present invention are not significantly impaired.

[0228] (Solvent)

[0229] It is preferable that at least one of the solvents in the hole injection layer-forming composition used in the wet film-forming method is a compound that can dissolve the constituent materials of the hole injection layer 3 .

[0230] When the hole injection layer-forming composition is the composition of the present invention, the solvent is the first solvent and the second solvent of the present invention.

[0231] Examples of the solvent include ether solvents, ester solvents, aromatic hydrocarbon solvents, and amide solvents.

[0232] Examples of the ether solvent include aliphatic ethers such as ethylene glycol dimethyl ether, ethylene glycol diethyl ether, and propylene glycol-1-monomethyl ether acetate (PGMEA); and aromatic ethers such as 1,2-dimethoxybenzene, 1,3-dimethoxybenzene, anisole, phenethyl ether, 2-methoxytoluene, 3-methoxytoluene, 4-methoxytoluene, 2,3-dimethylanisole, and 2,4-dimethylanisole.

[0233] Examples of the ester solvent include aromatic esters such as phenyl acetate, phenyl propionate, methyl benzoate, ethyl benzoate, propyl benzoate, and n-butyl benzoate.

[0234] Examples of the aromatic hydrocarbon solvent include toluene, xylene, cyclohexylbenzene, 3-isopropylbiphenyl, 1,2,3,4-tetramethylbenzene, 1,4-diisopropylbenzene, and methylnaphthalene.

[0235] Examples of the amide solvent include N,N-dimethylformamide and N,N-dimethylacetamide.

[0236] In addition, dimethyl sulfoxide or the like can also be used.

[0237] Among them, aromatic esters and aromatic ethers are preferred.

[0238] These solvents may be used alone or in any combination and ratio.

[0239] As long as the effect of the present invention is not significantly damaged, the concentration of the hole transport material in the hole injection layer forming composition is arbitrary. From the perspective of the uniformity of film thickness, the concentration of the hole transport material in the hole injection layer forming composition is preferably 0.01 weight % or more, more preferably 0.1 weight % or more, and more preferably 0.5 weight % or more. The concentration of the hole transport material in the hole injection layer forming composition is preferably 70 weight % or less, more preferably 60 weight % or less, and more preferably 50 weight % or less. From the perspective of not being easy to produce uneven film thickness, the concentration is preferably less. In addition, from the perspective of not being easy to produce defects in the hole injection layer formed into a film, the concentration is preferably larger.

[0240] (Formation of Hole Injection Layer by Wet Film Formation Method)

[0241] When the hole injection layer 3 is formed by a wet film-forming method, the material constituting the hole injection layer 3 is usually mixed with an appropriate solvent (a solvent for the hole injection layer) to prepare a film-forming composition (a composition for forming a hole injection layer). The composition for forming the hole injection layer 3 is applied to a layer corresponding to the lower layer of the hole injection layer (usually the anode 2) by an appropriate method to form a film, and then dried to form the hole injection layer 3.

[0242] (Formation of Hole Injection Layer 3 by Vacuum Deposition)

[0243] When the hole injection layer 3 is formed by vacuum deposition, the hole transport layer 3 can be formed as follows, for example. One or more constituent materials of the hole injection layer 3 (the aforementioned hole transport material, electron accepting compound, etc.) are placed in a crucible placed in a vacuum container (when two or more materials are used, they are placed in separate crucibles), and the vacuum container is evacuated to 10°C using an appropriate vacuum pump. -4 Then, the crucible is heated (when two or more materials are used, separate crucibles are heated), and the evaporation rate is controlled to cause evaporation (when two or more materials are used, the evaporation rate of each is independently controlled to cause evaporation), thereby forming a hole injection layer 3 on the anode 2 of the substrate 1 placed opposite the crucible. When two or more materials are used, a mixture of them can also be placed in a crucible, heated, and evaporated to form the hole injection layer 3.

[0244] The degree of vacuum during vapor deposition is not limited unless the effects of the present invention are significantly impaired. The degree of vacuum during vapor deposition is generally 0.1×10 -6 Torr(0.13×10 -4 Pa) and above 9.0×10 -6 Torr(12.0×10 -4 Pa) or less. As long as the effect of the present invention is not significantly impaired, the evaporation rate is not limited. The evaporation rate is generally Above and The film forming temperature during vapor deposition is not limited unless the effects of the present invention are significantly impaired. The film forming temperature during vapor deposition is preferably 10° C. or higher and 50° C. or lower.

[0245] [Hole Transport Layer]

[0246] The hole transport layer 4 is a layer that transports holes from the anode 2 to the light-emitting layer 5. The hole transport layer 4 is not an essential layer for the organic electroluminescent element of the present invention. However, when the hole transport layer 4 is provided, the hole transport layer 4 is usually formed on the hole injection layer 3 when the hole injection layer 3 is present, and is formed on the anode 2 when the hole injection layer 3 is not present.

[0247] The hole transport layer 4 may be formed by vacuum deposition or wet film formation without particular limitation. From the perspective of reducing dark spots, the hole transport layer 4 is preferably formed by wet film formation.

[0248] The material forming the hole transport layer 4 is preferably a material with high hole transport properties and capable of efficiently transporting injected holes. Therefore, the material forming the hole transport layer 4 preferably has a low ionization potential, high transparency to visible light, high hole mobility, excellent stability, and is less likely to generate impurities that can trap holes during manufacture or use. In most cases, the hole transport layer 4 is in contact with the light-emitting layer 5, so it is preferred that the hole transport layer 4 does not eliminate the light emitted by the light-emitting layer 5 or form exciplexes with the light-emitting layer 5, thereby reducing efficiency.

[0249] The material for the hole transport layer 4 may be any material that has been conventionally used as a constituent material of the hole transport layer 4. Examples of the material for the hole transport layer 4 include arylamine derivatives, fluorene derivatives, spiro derivatives, carbazole derivatives, pyridine derivatives, pyrazine derivatives, pyrimidine derivatives, triazine derivatives, quinoline derivatives, phenanthroline derivatives, phthalocyanine derivatives, porphyrin derivatives, silole derivatives, oligothiophene derivatives, condensed polycyclic aromatic derivatives, and metal complexes.

[0250] Examples of materials for the hole transport layer 4 include polyvinylcarbazole derivatives, polyarylamine derivatives, polyvinyltriphenylamine derivatives, polyfluorene derivatives, polyarylene derivatives, polyarylene ether sulfone derivatives containing tetraphenylbenzidine, polyarylene vinylene derivatives, polysiloxane derivatives, polythiophene derivatives, and poly(p-phenylene vinylene) derivatives. These may be alternating copolymers, random copolymers, block copolymers, or graft copolymers, and may also be polymers having branches in the main chain and three or more terminal ends, or so-called dendrimers.

[0251] Among them, as the material for the hole transport layer 4 , a polyarylamine derivative or a polyarylene derivative is preferable.

[0252] Specific examples of the polyarylamine derivative and the polyarylene derivative include the derivatives described in JP-A-2008-98619.

[0253] As the polyarylamine derivative, the above-mentioned aromatic tertiary amine polymer compound is preferably used.

[0254] When the hole transport layer 4 is formed by a wet film formation method, a composition for forming a hole transport layer is prepared in the same manner as in the formation of the hole injection layer 3 , and the composition is wet-formed and then dried.

[0255] The hole transport layer-forming composition contains a solvent in addition to the hole transport material. The solvent used is the same as that used in the hole injection layer-forming composition. Furthermore, the film formation and drying conditions are the same as those used for forming the hole injection layer 3.

[0256] When the hole transport layer-forming composition is the composition of the present invention, the solvent is the first solvent and the second solvent of the present invention.

[0257] When the hole transport layer 4 is formed by vacuum deposition, the film formation conditions and the like are the same as those for forming the hole injection layer 3 .

[0258] Taking into account factors such as infiltration of low molecular weight materials in the light-emitting layer and swelling of the hole transport material, the thickness of the hole transport layer 4 is usually 5 nm or more, preferably 10 nm or more, and usually 300 nm or less, preferably 200 nm or less.

[0259] [Luminous layer]

[0260] The light-emitting layer 5 is a layer that becomes the main light source by being excited by the recombination of holes injected from the anode 2 and electrons injected from the cathode 9 between the electrodes under an electric field. The light-emitting layer 5 is generally formed on the hole transport layer 4 when the hole transport layer 4 is present; on the hole injection layer 3 when the hole transport layer 4 is absent but the hole injection layer 3 is present; and on the anode 2 when neither the hole transport layer 4 nor the hole injection layer 3 is present.

[0261] <Materials for Light-Emitting Layer>

[0262] The material for the light-emitting layer generally contains a light-emitting material and a charge transport material serving as a main component.

[0263] <Luminescent Materials>

[0264] As the luminescent material, any known material used as a luminescent material for organic electroluminescent elements can be applied without particular limitation, as long as it emits light at the desired wavelength and has good luminous efficiency. The luminescent material may be a fluorescent material or a phosphorescent material, but from the perspective of internal quantum efficiency, a phosphorescent material is preferred. It is further preferred that the red and green luminescent materials be phosphorescent materials, and the blue luminescent material be a fluorescent material.

[0265] When the composition of the present invention is a composition for forming a light-emitting layer, it is preferable to use the following phosphorescent materials, fluorescent materials, and charge transport materials.

[0266] <Phosphorescent Materials>

[0267] Phosphorescent materials are materials that emit light from an excited triplet state, and are typically metal complex compounds containing Ir, Pt, Eu, etc., and preferably contain a metal complex.

[0268] Among the metal complexes, as phosphorescent organic metal complexes that emit light via a triplet state, examples include Werner-type complexes or organic metal complex compounds containing a metal selected from the long period periodic table (hereinafter, referred to as "periodic table" unless otherwise specified, in which case it refers to the long period periodic table) VIIB to IB groups as the central metal. As such phosphorescent materials, for example, phosphorescent materials described in International Publication No. 2014 / 024889, International Publication No. 2015-087961, International Publication No. 2016 / 194784, and Japanese Patent Application Laid-Open No. 2014-074000 can be cited. Preferably, it is a compound represented by the following formula (201) or a compound represented by the following formula (205), and more preferably a compound represented by the following formula (201).

[0269]

[0270] In formula (201), ring A1 represents an aromatic hydrocarbon ring structure which may have a substituent or an aromatic heterocyclic structure which may have a substituent.

[0271] Ring A2 represents an aromatic heterocyclic structure which may have a substituent.

[0272] R 201 、R 202 Each independently represents a structure represented by formula (202), and "*" represents a bonding position to ring A1 or ring A2. 201 、R 202 Can be the same or different, in R 201 、R 202 When a plurality of each are present, they may be the same or different.

[0273] Ar 201 、Ar 203 Each independently represents an aromatic hydrocarbon ring structure which may have a substituent or an aromatic heterocyclic structure which may have a substituent.

[0274] Ar 202 It represents an aromatic hydrocarbon ring structure which may have a substituent, an aromatic heterocyclic structure which may have a substituent, or an aliphatic hydrocarbon structure which may have a substituent.

[0275] Substituents bonded to ring A1, substituents bonded to ring A2, or substituents bonded to ring A1 and substituents bonded to ring A2 may bond to each other to form a ring.

[0276] B 201 -L 200 -B 202 Indicates an anionic bidentate ligand. B 201 and B 202 Each independently represents a carbon atom, an oxygen atom or a nitrogen atom, and these atoms may be atoms constituting a ring. 200 Indicates a single bond, or with B 201 and B 202 Atom groups that together form a bidentate ligand. 201 -L 200 -B 202 When there are multiple ones, they may be the same or different.

[0277] It should be noted that in formula (201) and formula (202),

[0278] i1 and i2 each independently represent an integer from 0 to 12,

[0279] i3 indicates that it can replace Ar 202 The number of is an integer greater than 0,

[0280] i4 indicates that it can replace Ar 201 The number of is an integer greater than 0,

[0281] k1 and k2 each independently represent an integer greater than or equal to 0, with the number of rings that can be substituted for ring A1 and ring A2 being the upper limit.

[0282] z represents an integer of 1 to 3.

[0283] (Substituent)

[0284] Unless otherwise specified, the substituent is preferably a group selected from the following substituent group S.

[0285] <Substituent Group S>

[0286] An alkyl group, preferably an alkyl group having 1 to 20 carbon atoms, more preferably an alkyl group having 1 to 12 carbon atoms, further preferably an alkyl group having 1 to 8 carbon atoms, and particularly preferably an alkyl group having 1 to 6 carbon atoms.

[0287] An alkoxy group, preferably an alkoxy group having 1 to 20 carbon atoms, more preferably an alkoxy group having 1 to 12 carbon atoms, and still more preferably an alkoxy group having 1 to 6 carbon atoms.

[0288] An aryloxy group, preferably an aryloxy group having 6 to 20 carbon atoms, more preferably an aryloxy group having 6 to 14 carbon atoms, further preferably an aryloxy group having 6 to 12 carbon atoms, and particularly preferably an aryloxy group having 6 carbon atoms.

[0289] A heteroaryloxy group, preferably a heteroaryloxy group having 3 to 20 carbon atoms, more preferably a heteroaryloxy group having 3 to 12 carbon atoms.

[0290] - Alkylamino group, preferably an alkylamino group having 1 to 20 carbon atoms, more preferably an alkylamino group having 1 to 12 carbon atoms.

[0291] An arylamino group, preferably an arylamino group having 6 to 36 carbon atoms, more preferably an arylamino group having 6 to 24 carbon atoms.

[0292] An aralkyl group, preferably an aralkyl group having 7 to 40 carbon atoms, more preferably an aralkyl group having 7 to 18 carbon atoms, and still more preferably an aralkyl group having 7 to 12 carbon atoms.

[0293] A heteroaralkyl group, preferably a heteroaralkyl group having 7 to 40 carbon atoms, more preferably a heteroaralkyl group having 7 to 18 carbon atoms.

[0294] An alkenyl group, preferably an alkenyl group having 2 to 20 carbon atoms, more preferably an alkenyl group having 2 to 12 carbon atoms, further preferably an alkenyl group having 2 to 8 carbon atoms, and particularly preferably an alkenyl group having 2 to 6 carbon atoms.

[0295] - Alkynyl group, preferably an alkynyl group having 2 to 20 carbon atoms, more preferably an alkynyl group having 2 to 12 carbon atoms.

[0296] An aryl group, preferably an aryl group having 6 to 30 carbon atoms, more preferably an aryl group having 6 to 24 carbon atoms, further preferably an aryl group having 6 to 18 carbon atoms, and particularly preferably an aryl group having 6 to 14 carbon atoms.

[0297] A heteroaryl group, preferably a heteroaryl group having 3 to 30 carbon atoms, more preferably a heteroaryl group having 3 to 24 carbon atoms, further preferably a heteroaryl group having 3 to 18 carbon atoms, and particularly preferably a heteroaryl group having 3 to 14 carbon atoms.

[0298] An alkylsilyl group, preferably an alkylsilyl group having 1 to 20 carbon atoms, more preferably an alkylsilyl group having 1 to 12 carbon atoms.

[0299] An arylsilyl group, preferably an arylsilyl group having 6 to 20 carbon atoms, more preferably an arylsilyl group having 6 to 14 carbon atoms.

[0300] - Alkylcarbonyl group, preferably an alkylcarbonyl group having 2 to 20 carbon atoms.

[0301] - Arylcarbonyl group, preferably an arylcarbonyl group having 7 to 20 carbon atoms.

[0302] Regarding the above groups, one or more hydrogen atoms may be substituted by fluorine atoms, or one or more hydrogen atoms may be substituted by deuterium atoms.

[0303] Unless otherwise specified, an aryl group is an aromatic hydrocarbon ring, and a heteroaryl group is an aromatic heterocycle.

[0304] · A hydrogen atom, a deuterium atom, a fluorine atom, a cyano group or -SF5.

[0305] Among the above-mentioned substituent group S, preferably alkyl, alkoxy, aryloxy, arylamino, aralkyl, alkenyl, aryl, heteroaryl, alkylsilyl, arylsilyl, and groups in which one or more hydrogen atoms of these groups are substituted by fluorine atoms, fluorine atoms, cyano or -SF5,

[0306] More preferably, it is an alkyl group, an arylamino group, an aralkyl group, an alkenyl group, an aryl group, a heteroaryl group, a group in which one or more hydrogen atoms of these groups are substituted by a fluorine atom, a fluorine atom, a cyano group or -SF5,

[0307] More preferably, they are alkyl, alkoxy, aryloxy, arylamino, aralkyl, alkenyl, aryl, heteroaryl, alkylsilyl, and arylsilyl.

[0308] Particularly preferred are alkyl, arylamino, aralkyl, alkenyl, aryl, and heteroaryl.

[0309] Most preferred are alkyl, arylamino, aralkyl, aryl, and heteroaryl.

[0310] These substituent groups S may further have a substituent selected from the substituent group S. Preferred groups, more preferred groups, further preferred groups, particularly preferred groups, and most preferred groups of the substituents that may be present are the same as the preferred groups in the substituent group S.

[0311] (Ring A1)

[0312] Ring A1 represents an aromatic hydrocarbon ring structure which may have a substituent or an aromatic heterocyclic structure which may have a substituent.

[0313] The aromatic hydrocarbon ring is preferably an aromatic hydrocarbon ring having 6 to 30 carbon atoms. Specifically, a benzene ring, a naphthalene ring, an anthracene ring, a triphenylyl ring, an acenaphthene ring, a fluoranthene ring, and a fluorene ring are preferred.

[0314] The aromatic heterocyclic ring is preferably an aromatic heterocyclic ring having 3 to 30 carbon atoms and containing any one of a nitrogen atom, an oxygen atom, or a sulfur atom as a heteroatom. A furan ring, a benzofuran ring, a thiophene ring, or a benzothiophene ring is more preferred.

[0315] Ring A1 is more preferably a benzene ring, a naphthalene ring, or a fluorene ring, particularly preferably a benzene ring or a fluorene ring, and most preferably a benzene ring.

[0316] (Ring A2)

[0317] Ring A2 represents an aromatic heterocyclic structure which may have a substituent.

[0318] The aromatic heterocyclic ring is preferably an aromatic heterocyclic ring having 3 to 30 carbon atoms and containing any one of a nitrogen atom, an oxygen atom, or a sulfur atom as a heteroatom. Specific examples thereof include a pyridine ring, a pyrimidine ring, a pyrazine ring, a triazine ring, an imidazole ring, Azole ring, thiazole ring, benzothiazole ring, benzo azole ring, benzimidazole ring, quinoline ring, isoquinoline ring, quinoxaline ring, quinazoline ring, naphthyridine ring, phenanthridine ring, preferably pyridine ring, pyrazine ring, pyrimidine ring, imidazole ring, benzothiazole ring, benzo azole ring, quinoline ring, isoquinoline ring, quinoxaline ring, quinazoline ring, more preferably pyridine ring, imidazole ring, benzothiazole ring, quinoline ring, isoquinoline ring, quinoxaline ring, quinazoline ring, most preferably pyridine ring, imidazole ring, benzothiazole ring, quinoline ring, quinoxaline ring, quinazoline ring.

[0319] (Combination of Ring A1 and Ring A2)

[0320] Preferred combinations of Ring A1 and Ring A2, when expressed as (Ring A1-Ring A2), are (benzene ring-pyridine ring), (benzene ring-quinoline ring), (benzene ring-quinoxaline ring), (benzene ring-quinazoline ring), (benzene ring-benzothiazole ring), (benzene ring-imidazole ring), (benzene ring-pyrrole ring), (benzene ring-oxadiazole ring), and (benzene ring-thiophene ring).

[0321] (Substituents of Ring A1 and Ring A2)

[0322] The substituent that Ring A1 and Ring A2 may have can be arbitrarily selected, but is preferably one or more substituents selected from the above-mentioned substituent group S.

[0323] (Ar 201 、Ar 202 、Ar 203 )

[0324] Ar 201 、Ar 203 Each independently represents an aromatic hydrocarbon ring structure which may have a substituent or an aromatic heterocyclic structure which may have a substituent.

[0325] Ar 202 It represents an aromatic hydrocarbon ring structure which may have a substituent, an aromatic heterocyclic structure which may have a substituent, or an aliphatic hydrocarbon structure which may have a substituent.

[0326] Ar 201 、Ar 202 、Ar 203 When any one of the above is an aromatic hydrocarbon ring structure which may have a substituent, the aromatic hydrocarbon ring structure is preferably an aromatic hydrocarbon ring having 6 to 30 carbon atoms. Specifically, a benzene ring, a naphthalene ring, an anthracene ring, a triphenyl ring, an acenaphthene ring, a fluoranthene ring, or a fluorene ring is preferred, a benzene ring, a naphthalene ring, or a fluorene ring is more preferred, and a benzene ring is most preferred.

[0327] Ar 201 、Ar 202 When any one of them is a benzene ring which may have a substituent, it is preferred that at least one benzene ring is bonded to the adjacent structure at the ortho position or the meta position, and it is more preferred that at least one benzene ring is bonded to the adjacent structure at the meta position.

[0328] Ar 201 、Ar 202 、Ar 203 When any one of them is a fluorene ring which may have a substituent, the 9-position and 9'-position of the fluorene ring preferably have a substituent or are bonded to an adjacent structure.

[0329] Ar 201 、Ar 202 、Ar 203 When any one of the aromatic heterocyclic structure is an aromatic heterocyclic structure which may have a substituent, the aromatic heterocyclic structure is preferably an aromatic heterocyclic ring having 3 to 30 carbon atoms and containing any one of a nitrogen atom, an oxygen atom or a sulfur atom as a heteroatom, and specifically includes a pyridine ring, a pyrimidine ring, a pyrazine ring, a triazine ring, an imidazole ring, Azole ring, thiazole ring, benzothiazole ring, benzo azole ring, benzimidazole ring, quinoline ring, isoquinoline ring, quinoxaline ring, quinazoline ring, naphthyridine ring, phenanthridine ring, carbazole ring, dibenzofuran ring, dibenzothiophene ring, preferably pyridine ring, pyrimidine ring, triazine ring, carbazole ring, dibenzofuran ring, dibenzothiophene ring.

[0330] Ar 201 、Ar 202 、Ar 203 When any one of them is a carbazole ring which may have a substituent, the N position of the carbazole ring preferably has a substituent or is bonded to an adjacent structure.

[0331] Ar 202 When it is an aliphatic hydrocarbon structure that may have a substituent, it is a linear, branched or cyclic aliphatic hydrocarbon structure, preferably having 1 to 24 carbon atoms, more preferably 1 to 12 carbon atoms, and even more preferably 1 to 8 carbon atoms.

[0332] (i1, i2, i3, i4, k1, k2)

[0333] i1 and i2 each independently represent an integer of 0 to 12, preferably 1 to 12, more preferably 1 to 8, and further preferably 1 to 6. Within this range, improvement in solubility and charge transport properties can be expected.

[0334] i3 preferably represents an integer of 0 to 5, more preferably 0 to 2, and even more preferably 0 or 1.

[0335] i4 preferably represents an integer of 0 to 2, and more preferably 0 or 1.

[0336] k1 and k2 each independently represent an integer of preferably 0 to 3, more preferably 1 to 3, further preferably 1 or 2, and particularly preferably 1.

[0337] (Ar 201 、Ar 202 、Ar 203 Preferred substituents)

[0338] Ar 201 、Ar 202 、Ar 203 The substituents that may be present can be selected arbitrarily, but are preferably one or more substituents selected from the above-mentioned substituent group S. Preferred groups are also shown in the above-mentioned substituent group S, but are more preferably unsubstituted (hydrogen atom), alkyl, aryl, particularly preferably unsubstituted (hydrogen atom), alkyl, most preferably unsubstituted (hydrogen atom) or tert-butyl, and tert-butyl is preferably present in the presence of Ar 203 In the case of substitution with Ar 203 , in the absence of Ar 203 In the case of substitution with Ar 202 , in the absence of Ar 202 and Ar 203 In the case of substitution with Ar 201 .

[0339] (Preferred embodiment of the compound represented by formula (201))

[0340] The compound represented by the above formula (201) is preferably a compound that satisfies at least one of the following (I) to (IV).

[0341] (I) Phenylene connection formula

[0342] The structure represented by formula (202) preferably has a structure of a group formed by connecting benzene rings, that is, a benzene ring structure, i1 is 1 to 6, and at least one of the benzene rings is bonded to an adjacent structure at the ortho position or the meta position.

[0343] By adopting such a structure, improvement in solubility and improvement in charge transport properties can be expected.

[0344] (II) (phenylene)-aralkyl (alkyl)

[0345] It has a structure in which an alkyl group or an aralkyl group is bonded to ring A1 or ring A2, and an aromatic hydrocarbon group or an aromatic heterocyclic group, that is, Ar 201 is an aromatic hydrocarbon structure or an aromatic heterocyclic structure, i1 is 1 to 6, Ar 202 is an aliphatic hydrocarbon structure, i2 is 1 to 12, preferably 3 to 8, and Ar 203 is a benzene ring structure, i3 is 0 or 1, preferably Ar 201 The aromatic hydrocarbon structure is preferably a structure in which 1 to 5 benzene rings are linked together, and more preferably a single benzene ring.

[0346] By adopting such a structure, improvement in solubility and improvement in charge transport properties can be expected.

[0347] (III) dendron

[0348] A structure with a dendron bonded to ring A1 or ring A2, such as Ar 201 、Ar 202 It is a benzene ring structure, Ar 203 It is a biphenyl or terphenyl structure, i1 and i2 are 1 to 6, i3 is 2, and j is 2.

[0349] By adopting such a structure, improvement in solubility and improvement in charge transport properties can be expected.

[0350] (IV)B 201 -L 200 -B 202

[0351] B 201 -L 200 -B 202 The structure shown is preferably a structure shown by the following formula (203) or the following formula (204).

[0352]

[0353] In formula (203), R 211 、R 212 、R 213 Each independently represents a substituent.

[0354] In formula (204), ring B3 represents an aromatic heterocyclic structure containing a nitrogen atom which may have a substituent. Ring B3 is preferably a pyridine ring.

[0355] (Preferred phosphorescent material)

[0356] The phosphorescent material represented by the above formula (201) is not particularly limited, but the following phosphorescent materials can be cited as preferred phosphorescent materials.

[0357]

[0358]

[0359] In addition, a phosphorescent material represented by the following formula (205) is also preferred.

[0360]

[0361] [In formula (205), M 2 R represents a metal, and T represents a carbon atom or a nitrogen atom. 92 ~R 95 Each independently represents a substituent. However, when T is a nitrogen atom, R 94 and R 95 ]

[0362] In formula (205), as M 2 Specific examples include metals selected from Groups VIIB to IB of the periodic table. Among them, ruthenium, rhodium, palladium, silver, rhenium, osmium, iridium, platinum, or gold are preferred, and divalent metals such as platinum and palladium are particularly preferred.

[0363] In addition, in formula (205), R 92 and R 93 Each independently represents a hydrogen atom, a halogen atom, an alkyl group, an aralkyl group, an alkenyl group, a cyano group, an amino group, an acyl group, an alkoxycarbonyl group, a carboxyl group, an alkoxy group, an alkylamino group, an aralkylamino group, a haloalkyl group, a hydroxyl group, an aryloxy group, an aromatic hydrocarbon group, or an aromatic heterocyclic group.

[0364] Furthermore, when T is a carbon atom, R 94 and R 95 Each independently represents the 92 and R 93 In addition, when T is a nitrogen atom, there is no R directly bonded to the T. 94 or R 95 In addition, R 92 ~R 95 It may further have a substituent. As a substituent, it may be the substituent mentioned above. 92 ~R 95 Any two or more groups in the group may be linked to each other to form a ring.

[0365] (Molecular weight)

[0366] The molecular weight of the phosphorescent material is preferably 5000 or less, more preferably 4000 or less, and particularly preferably 3000 or less. Furthermore, the molecular weight of the phosphorescent material is preferably 800 or more, more preferably 1000 or more, and even more preferably 1200 or more. It is believed that by having a molecular weight within this range, the phosphorescent material is uniformly mixed with the charge transport material without agglomerating with each other, thereby enabling a light-emitting layer with high luminous efficiency to be obtained.

[0367] The molecular weight of the phosphorescent material is preferably large, considering the advantages of high Tg, melting point, decomposition temperature, excellent heat resistance of the phosphorescent material and the resulting light-emitting layer, and the low incidence of degradation of film quality due to gas generation, recrystallization, and molecular migration, or increase in impurity concentration associated with thermal decomposition of the material. On the other hand, the molecular weight of the phosphorescent material is preferably small, considering the ease of purification of the organic compound.

[0368] <Charge Transport Materials>

[0369] The charge transport material used in the light-emitting layer is a material having a skeleton with excellent charge transport properties, and is preferably selected from electron transport materials, hole transport materials, and bipolar materials capable of transporting both electrons and holes.

[0370] Specific examples of the skeleton having excellent charge transport properties include an aromatic structure, an aromatic amine structure, a triarylamine structure, a dibenzofuran structure, a naphthalene structure, a phenanthrene structure, a phthalocyanine structure, a porphyrin structure, a thiophene structure, a benzylphenyl structure, a fluorene structure, a quinacridone structure, a triphenylene structure, a carbazole structure, a pyrene structure, an anthracene structure, a phenanthroline structure, a quinoline structure, a pyridine structure, a pyrimidine structure, a triazine structure, oxadiazole structure or imidazole structure, etc.

[0371] As the electron transport material, from the viewpoint of being a material having excellent electron transport properties and a relatively stable structure, a compound having a pyridine structure, a pyrimidine structure, or a triazine structure is more preferable, and a compound having a pyrimidine structure or a triazine structure is even more preferable.

[0372] The hole transport material is a compound having a structure with excellent hole transport properties. Among the above-mentioned central skeletons with excellent charge transport properties, the structure with excellent hole transport properties is preferably a carbazole structure, a dibenzofuran structure, a triarylamine structure, a naphthalene structure, a phenanthrene structure or a pyrene structure, and more preferably a carbazole structure, a dibenzofuran structure or a triarylamine structure.

[0373] The charge transport material used in the light-emitting layer preferably has a fused ring structure of three or more rings, and more preferably a compound having two or more fused ring structures of three or more rings or a compound having at least one fused ring of five or more rings. By using these compounds, it is easy to increase the rigidity of the molecule and suppress the degree of molecular motion in response to heat. Furthermore, from the aspects of charge transportability and material durability, it is preferred that the fused rings of three or more rings and the fused rings of five or more rings have aromatic hydrocarbon rings or aromatic heterocycles.

[0374] Specific examples of the fused ring structure having three or more rings include an anthracene structure, a phenanthrene structure, a pyrene structure, The structure of the present invention may be a tetracene structure, a triphenylene structure, a fluorene structure, a benzofluorene structure, an indenofluorene structure, an indolofluorene structure, a carbazole structure, an indenocarbazole structure, an indolocarbazole structure, a dibenzofuran structure, a dibenzothiophene structure, etc. From the viewpoint of charge transport and solubility, at least one structure selected from the group consisting of a phenanthrene structure, a fluorene structure, an indenofluorene structure, a carbazole structure, an indenocarbazole structure, an indolocarbazole structure, a dibenzofuran structure, and a dibenzothiophene structure is preferred. From the viewpoint of durability against charge, a carbazole structure or an indolocarbazole structure is more preferred.

[0375] In the present invention, from the viewpoint of durability of the organic electroluminescent element against charge, it is preferred that at least one of the charge transport materials in the light-emitting layer is a material having a pyrimidine skeleton or a triazine skeleton.

[0376] From the perspective of excellent flexibility, the charge transport material of the light-emitting layer is preferably a polymer material. A light-emitting layer formed using a material with excellent flexibility is preferably used as the light-emitting layer of an organic electroluminescent element formed on a flexible substrate. When the charge transport material contained in the light-emitting layer is a polymer material, the molecular weight is preferably 5,000 to 1,000,000, more preferably 10,000 to 500,000, and even more preferably 10,000 to 100,000.

[0377] Furthermore, from the perspectives of ease of synthesis and purification, ease of designing electron and hole transport properties, and ease of viscosity adjustment when dissolved in a solvent, the charge transport material for the light-emitting layer is preferably a low molecular weight material. When the charge transport material contained in the light-emitting layer is a low molecular weight material, the molecular weight is preferably 5000 or less, more preferably 4000 or less, particularly preferably 3000 or less, most preferably 2000 or less, preferably 300 or more, more preferably 350 or more, and even more preferably 400 or more.

[0378] <Fluorescent Materials>

[0379] The fluorescent material is not particularly limited, but is preferably a compound represented by the following formula (211).

[0380]

[0381] In the above formula (211), Ar 241 represents an aromatic hydrocarbon condensed ring structure which may have a substituent, Ar 242 、Ar 243 Each independently represents an alkyl group, an aromatic hydrocarbon group, an aromatic hetero group, or a group formed by bonding thereof which may have a substituent. n41 is an integer of 1-4.

[0382] Ar 241 It preferably represents an aromatic hydrocarbon condensed ring structure having 10 to 30 carbon atoms, and specific examples of the ring structure include naphthalene, acenaphthene, fluorene, anthracene, phenanthrene, fluoranthene, pyrene, tetracene, Perylene, etc.

[0383] Ar 241 More preferably, it is an aromatic hydrocarbon condensed ring structure having 12 to 20 carbon atoms. Specific examples of the ring structure include acenaphthene, fluorene, anthracene, phenanthrene, fluoranthene, pyrene, tetracene, Perylene.

[0384] Ar 241 More preferably, it is an aromatic hydrocarbon condensed ring structure having 16 to 18 carbon atoms. Specific examples of the ring structure include fluoranthene, pyrene,

[0385] n41 is 1 to 4, preferably 1 to 3, more preferably 1 to 2, and most preferably 2.

[0386] As Ar 242 、Ar 243 The alkyl group is preferably an alkyl group having 1 to 12 carbon atoms, and more preferably an alkyl group having 1 to 6 carbon atoms.

[0387] As Ar 242 、Ar 243 The aromatic hydrocarbon group is preferably an aromatic hydrocarbon group having 6 to 30 carbon atoms, more preferably an aromatic hydrocarbon group having 6 to 24 carbon atoms, and most preferably a phenyl group or a naphthyl group.

[0388] As Ar 242 、Ar 243 The aromatic hetero group is preferably an aromatic hetero group having 3 to 30 carbon atoms, more preferably an aromatic hydrocarbon group having 5 to 24 carbon atoms, specifically, preferably a carbazolyl group, a dibenzofuranyl group, or a dibenzothiophenyl group, more preferably a dibenzofuranyl group.

[0389] Ar 241 、Ar 242 、Ar 243The substituent that may be possessed is preferably a group selected from the above-mentioned substituent group S, more preferably a hydrocarbon group included in the substituent group S, and even more preferably a hydrocarbon group among the groups preferred as the substituent group S.

[0390] The charge transport material used together with the fluorescent material is not particularly limited, but a charge transport material represented by the following formula (212) is preferred.

[0391]

[0392] In the above formula (212), R 251 、R 252 Each independently represents the structure shown in formula (213), R 253 represents a substituent, R 253 When there are multiple members, they may be the same or different, and n43 is an integer of 0-8.

[0393]

[0394] In the above formula (213), * represents the bonding site with the anthracene ring of formula (212), Ar 254 、Ar 255 Each independently represents an aromatic hydrocarbon structure which may have a substituent or a heteroaromatic ring structure which may have a substituent, Ar 254 、Ar 255 When a plurality of them exist, they may be the same or different, n44 is an integer of 1 to 5, and n45 is an integer of 0 to 5.

[0395] Ar 254 It is preferably a monocyclic or condensed aromatic hydrocarbon structure having 6 to 30 carbon atoms which may have a substituent, and more preferably a monocyclic or condensed aromatic hydrocarbon structure having 6 to 12 carbon atoms which may have a substituent.

[0396] Ar 255 Preferably, it is a monocyclic or condensed aromatic hydrocarbon structure having 6 to 30 carbon atoms which may have a substituent, or a condensed aromatic heterocyclic structure having 6 to 30 carbon atoms which may have a substituent. 255 More preferably, it is a monocyclic or condensed aromatic hydrocarbon structure having 6 to 12 carbon atoms which may have a substituent, or a condensed aromatic heterocyclic structure having 12 carbon atoms which may have a substituent.

[0397] n44 is preferably an integer of 1 to 3, more preferably 1 or 2.

[0398] n45 is preferably an integer of 0-3, more preferably 0-2.

[0399] R as a substituent 253 、Ar 254 and Ar255 The substituent that may be present is preferably a group selected from the above-mentioned substituent group S. More preferably, it is a hydrocarbon group included in the substituent group S, and even more preferably, it is a hydrocarbon group among the groups preferred as the substituent group S.

[0400] The molecular weight of the fluorescent material and the charge transport material is preferably 5000 or less, more preferably 4000 or less, particularly preferably 3000 or less, and most preferably 2000 or less. It is preferably 300 or more, more preferably 350 or more, and even more preferably 400 or more.

[0401] [Hole blocking layer]

[0402] A hole blocking layer 6 may be provided between the light-emitting layer 5 and the electron injection layer 8 described later. The hole blocking layer 6 is a layer in the electron transport layer that further functions to block holes moving from the anode 2 from reaching the cathode 9. The hole blocking layer 6 is a layer stacked on the light-emitting layer 5 so as to be in contact with the interface of the light-emitting layer 5 on the cathode 9 side.

[0403] The hole blocking layer 6 has the function of blocking holes moving from the anode 2 from reaching the cathode 9 and the function of efficiently transporting electrons injected from the cathode 9 toward the light-emitting layer 5 .

[0404] Examples of the physical properties required of the material constituting the hole blocking layer 6 include high electron mobility and low hole mobility, a large energy gap (difference between HOMO and LUMO), and a high excited triplet energy level (T1). As materials for the hole blocking layer 6 that meet such conditions, for example, there can be mentioned mixed ligand complexes such as bis(2-methyl-8-hydroxyquinolinolato)(phenol)aluminum, bis(2-methyl-8-hydroxyquinolinolato)(triphenylsilanol)aluminum, metal complexes such as bis(2-methyl-8-hydroxyquinolinolato)aluminum-μ-oxo-bis-(2-methyl-8-hydroxyquinolinolato)aluminum binuclear metal complexes, styryl compounds such as distyrylbiphenyl derivatives (Japanese Patent Publication No. 11-242996), triazole derivatives such as 3-(4-biphenyl)-4-phenyl-5(4-tert-butylphenyl)-1,2,4-triazole (Japanese Patent Publication No. 7-41759), and phenanthroline derivatives such as bathocuproin (Japanese Patent Publication No. 10-79297). Furthermore, compounds having at least one pyridine ring substituted at the 2-, 4-, or 6-positions, as described in International Publication No. 2005 / 022962, are also preferably used as the material for the hole-blocking layer 6 .

[0405] The method for forming the hole blocking layer 6 is not limited. The hole blocking layer 6 can be formed by a wet film forming method, a vapor deposition method, or other methods.

[0406] The thickness of the hole blocking layer 6 is arbitrary as long as the effects of the present invention are not significantly impaired. The thickness of the hole blocking layer 6 is usually 0.3 nm or more, preferably 0.5 nm or more, and usually 100 nm or less, preferably 50 nm or less.

[0407] [Electron transport layer]

[0408] The electron transport layer 7 is a layer provided between the optical layer 5 and the cathode 9 for transporting electrons.

[0409] As the electron transport material of the electron transport layer 7, a compound having a high electron injection effect from the cathode 9 or the adjacent layer on the cathode 9 side and a high electron mobility, which can efficiently transport the injected electrons, is generally used. Examples of compounds that meet such conditions include metal complexes such as aluminum complexes and lithium complexes of 8-hydroxyquinoline (Japanese Patent Application Laid-Open No. 59-194393), metal complexes of 10-hydroxybenzo[h]quinoline, Oxadiazole derivatives, distyryl biphenyl derivatives, silole derivatives, 3-hydroxyflavone metal complexes, 5-hydroxyflavone metal complexes, benzo Azole metal complexes, benzothiazole metal complexes, tribenzimidazolylbenzene (U.S. Patent No. 5,645,948), quinoxaline compounds (Japanese Patent Application Publication No. 6-207169), phenanthroline derivatives (Japanese Patent Application Publication No. 5-331459), 2-tert-butyl-9,10-N,N'-dicyanoanthraquinone diimine, triazine compound derivatives, n-type hydrogenated amorphous silicon carbide, n-type zinc sulfide, n-type zinc selenide, etc.

[0410] As the electron transport material used in the electron transport layer 7, by doping sodium, potassium, cesium, lithium, rubidium and other alkali metals in the electron transport organic compound represented by the metal complex such as the nitrogen-containing heterocyclic compound such as bathophenanthroline and the aluminum complex of 8-hydroxyquinoline (described in Japanese Patent Application Laid-Open No. 10-270171, Japanese Patent Application Laid-Open No. 2002-100478, Japanese Patent Application Laid-Open No. 2002-100482, etc.), it is possible to take into account both electron injection transport and excellent film quality, and thus it is preferred. In addition, it is also effective to dope inorganic salts such as lithium fluoride and cesium carbonate in the above-mentioned electron transport organic compound.

[0411] The method for forming the electron transport layer 7 is not limited. The electron transport layer 7 can be formed by a wet film formation method, a vapor deposition method, or other methods.

[0412] The thickness of the electron transport layer 7 is arbitrary as long as the effects of the present invention are not significantly impaired. The thickness of the electron transport layer 7 is usually 1 nm or more, preferably 5 nm or more, and usually 300 nm or less, preferably 100 nm or less.

[0413] [Electron injection layer]

[0414] In order to efficiently inject electrons injected from the cathode 9 into the light-emitting layer 5, an electron injection layer 8 may be provided between the electron transport layer 7 and the cathode 9 described later. The electron injection layer 8 is composed of an inorganic salt or the like.

[0415] Examples of materials for the electron injection layer 8 include lithium fluoride (LiF), magnesium fluoride (MgF2), lithium oxide (Li2O), and cesium (II) carbonate (CsCO3) (see Applied Physics Letters, 1997, Vol. 70, pp. 152; Japanese Patent Application Publication No. 10-74586; IEEE Transactions on Electron Devices, 1997, Vol. 44, pp. 1245; SID 04 Digest, pp. 154, etc.).

[0416] The electron injection layer 8 often does not have charge transport properties, and therefore is preferably used as an extremely thin film for efficient electron injection. The film thickness is usually 0.1 nm or more, and preferably 5 nm or less.

[0417] [cathode]

[0418] The cathode 9 is an electrode that plays a role in injecting electrons into the layer on the light-emitting layer 5 side.

[0419] Examples of materials for the cathode 9 include metals such as aluminum, gold, silver, nickel, palladium, and platinum; metal oxides such as indium and / or tin oxides; metal halides such as copper iodide; carbon black; or conductive polymers such as poly(3-methylthiophene), polypyrrole, and polyaniline. Among these, metals with a low work function are preferred for efficient electron injection. For example, suitable metals such as tin, magnesium, indium, calcium, aluminum, and silver, or alloys thereof, can be used. Specific examples include low-work-function alloy electrodes such as magnesium-silver alloys, magnesium-indium alloys, and aluminum-lithium alloys.

[0420] As the material of the cathode 9 , only one kind may be used, or two or more kinds may be used in combination in any combination and ratio.

[0421] The thickness of cathode 9 varies depending on the desired transparency. When transparency is required, the transmittance of visible light is preferably 60% or greater, preferably 80% or greater. In this case, the thickness of cathode 9 is typically 5 nm or greater, preferably 10 nm or greater, and typically 1000 nm or less, preferably approximately 500 nm or less. When opacity is desired, the thickness of cathode 9 is arbitrary and can be the same thickness as the substrate.

[0422] Different conductive materials may be stacked on the cathode 9 .

[0423] For example, if a metal cathode having a low work function, such as an alkali metal such as sodium or cesium, or an alkaline earth metal such as barium or calcium, is further laminated with a metal layer having a high work function and being stable relative to the atmosphere, the stability of the element is increased, which is preferred. For this purpose, metals such as aluminum, silver, copper, nickel, chromium, gold, and platinum can be used. These materials may be used alone or in any combination and ratio.

[0424] [Other layers]

[0425] The organic electroluminescent element of the present invention may have other structures within the scope of the present invention. For example, as long as its performance is not impaired, any layer other than the layers described above may be included between the anode 2 and the cathode 9, and layers not required in the layers described above may be omitted.

[0426] In the layer structure described above, the components other than the substrate may be stacked in the reverse order. Figure 1 If the layer structure is a cathode 9, an electron injection layer 8, an electron transport layer 7, a hole blocking layer 6, a light-emitting layer 5, a hole transport layer 4, a hole injection layer 3, and an anode 2, other components can be arranged on the substrate 1 in the order of cathode 9, electron injection layer 8, electron transport layer 7, hole blocking layer 6, light-emitting layer 5, hole transport layer 4, hole injection layer 3, and anode 2.

[0427] The organic electroluminescent element of the present invention can be configured as a single organic electroluminescent element, or can be applied to a structure in which a plurality of organic electroluminescent elements are arranged in an array, or can be applied to a structure in which anodes and cathodes are arranged in an XY matrix.

[0428] Each of the above-mentioned layers may contain components other than the components described as materials, unless the effects of the present invention are significantly impaired.

[0429] <Organic electroluminescent equipment>

[0430] An organic electroluminescent device such as an organic EL display device or an organic EL lighting device can be fabricated by providing two or more organic electroluminescent elements that emit light in different colors. By using the organic electroluminescent element of the present invention as at least one, and preferably all, of the organic electroluminescent elements in such an organic electroluminescent device, a high-quality organic electroluminescent device can be provided.

[0431] <Organic EL Display Device>

[0432] There are no particular restrictions on the type and structure of the organic EL display device using the organic electroluminescent element of the present invention, and the organic EL display device can be assembled using the organic electroluminescent element of the present invention according to a conventional method.

[0433] For example, an organic EL display device can be formed by a method described in "Organic EL Display" (published by Ohm Co., Ltd. on August 20, 2001, by Shizuo Tokito, Chihaya Adachi, and Hideyuki Murata).

[0434] <Organic EL Lighting>

[0435] There are no particular restrictions on the type and structure of the organic EL lighting using the organic electroluminescent element of the present invention, and the organic EL lighting can be assembled using the organic electroluminescent element of the present invention in accordance with conventional methods.

[0436] Example

[0437] The present invention will be described in more detail below with reference to Examples. However, the present invention is not limited to the following Examples, and the present invention can be implemented with any modifications without departing from the spirit of the present invention.

[0438] [Solvents used]

[0439] The physical properties of the solvents used in the following Examples and Comparative Examples are shown in Table 1 below.

[0440] [Table 1]

[0441]

[0442] “-” in the table means not determined

[0443] [Evaluation I: Evaluation of Flatness of the Panel Center]

[0444] <Preparation of Substrate 1>

[0445] An indium tin oxide (ITO) film was deposited on a 0.7 mm thick glass substrate by sputtering. A liquid-repellent acrylic resin was applied to the resulting substrate by spin coating to a thickness of 1.7 μm. Openings were then created using standard photolithography. The openings had a major axis of approximately 170 μm and a minor axis of approximately 50 μm.

[0446] <Coating of Base Layer 1>

[0447] A composition for base layer 1 is prepared by dissolving a base layer having an aromatic amine polymer as the main component in a solvent. The base layer 1 composition is applied to the above-mentioned opening of substrate 1 using an inkjet printer (DMP-2831 manufactured by Fujifilm Corporation), and the film is formed into a film with a thickness of about 30 nm by vacuum drying and calcining.

[0448] <Coating of Base Layer 2>

[0449] A composition for base layer 2 is prepared by dissolving a base layer having an aromatic amine polymer as the main component in a solvent. The composition for base layer 2 is applied to the base layer 1 in the above-mentioned opening using an inkjet printer (DMP-2831 manufactured by Fujifilm Corporation), and the mixture is vacuum dried and calcined to form a film with a thickness of about 20 nm.

[0450] <Preparation of Solid Component for Light-Emitting Layer Formation>

[0451] The charge injection transport materials, compound (H-1) and compound (H-2), and the light emitting material, (D-1) were mixed at a weight ratio of 30:70:20 to prepare a light emitting layer forming solid component I-1.

[0452]

[0453] <Definition of Flatness>

[0454] The cross-sectional view of the organic film formed within the opening, taken along a plane perpendicular to the surface of the organic film, is defined as the cross-sectional distribution of the organic film. The average film thickness Da of the organic film at lengths between 25% and 75% of the opening length in the cross-sectional distribution of the organic film is calculated. The region where the film thickness Do(x) of the organic film at a certain position x satisfies the following equation is defined as X1.

[0455] Da-Da×5%<Do(x)<Da+Da×5% (Formula 1)

[0456] When the length of the opening is defined as X2, the flatness is defined as X1 / X2×100(%).

[0457] <Reference Example 1>

[0458] Diethyl phthalate and cyclohexylbenzene were mixed at a weight ratio of 15:85 to prepare an organic solvent I-1. A light-emitting layer-forming solid component I-1 was dissolved in the organic solvent I-1 to give 1.7 wt % to prepare a light-emitting layer-forming composition I-1.

[0459] Using an inkjet printer (DMP-2831 manufactured by Fujifilm Corporation), five drops of the light-emitting layer-forming composition I-1 were applied to the base layer 2 in the opening. The composition I-1 was then dried by vacuum drying to remove the organic solvent and calcined at 120°C for 3 minutes to form the light-emitting layer I-1, a functional film.

[0460] In order to evaluate the flatness of the light-emitting layer I-1, a stylus-type surface step meter (ET200 manufactured by Kosaka Research Institute Co., Ltd.) was used to measure the ITO substrate formed with an organic film. The surface step is measured by scanning the long axis direction of the opening, obtaining two portions of the step distribution of the light-emitting layer I-1 near the center of the substrate, and averaging them to make a step distribution of the light-emitting layer I-1. Similarly, two portions of the distribution of the opening portion without any coating were obtained, and averaged to make a blank profile. Then, the two distributions of the light-emitting layer I-1 and the blank are overlapped to show how the organic film is formed in the opening portion. If the flatness is calculated according to the above definition, it is 93.8%. The distribution of the light-emitting layer I-1 and the blank is shown in Figure 1 .

[0461] <Reference Example 2>

[0462] 2-Phenoxyethyl acetate and ethyl benzoate were mixed at a weight ratio of 30:70 to prepare organic solvent I-2. Solid component I-1 for forming a light-emitting layer was dissolved in organic solvent I-2 to give 1.7 wt % to prepare light-emitting layer-forming composition I-2.

[0463] A light-emitting layer I-2 was formed in the same manner as in Reference Example 1 except that the light-emitting layer-forming composition I-2 was used instead of the light-emitting layer-forming composition I-1. The flatness of the light-emitting layer I-2 was evaluated in the same manner. The result, calculated using the above definition, was 96.2%. The distribution of the light-emitting layer I-2 and the blank is shown in FIG. Figure 2 .

[0464] <Comparative Example 1>

[0465] Dibenzyl ether and cyclohexylbenzene were mixed at a weight ratio of 20:80 to prepare organic solvent I-3. Solid component I-1 for forming a light-emitting layer was dissolved in organic solvent I-3 to give 1.7 wt % to prepare composition I-3 for forming a light-emitting layer.

[0466] A light-emitting layer I-3 was formed in the same manner as in Reference Example 1 except that the light-emitting layer-forming composition I-3 was used instead of the light-emitting layer-forming composition I-1. The flatness of the light-emitting layer I-3 was evaluated in the same manner. The result, calculated using the above definition, was 50.1%. The distribution of the light-emitting layer I-3 and the blank is shown in FIG. Figure 3 .

[0467] <Comparative Example 2>

[0468] 3-Phenoxytoluene and cyclohexylbenzene were mixed at a weight ratio of 20:80 to prepare organic solvent I-4. Solid component I-1 for forming a light-emitting layer was dissolved in organic solvent I-4 to give 1.7 wt % of light-emitting layer-forming composition I-4.

[0469] A light-emitting layer I-4 was formed in the same manner as in Reference Example 1 except that the light-emitting layer-forming composition I-4 was used instead of the light-emitting layer-forming composition I-1. The flatness of the light-emitting layer I-4 was evaluated in the same manner. The result, calculated using the above definition, was 67.7%. The distribution of the light-emitting layer I-4 and the blank is shown in FIG. Figure 4 .

[0470] <Comparative Example 3>

[0471] 2-Phenoxyethanol and cyclohexylbenzene were mixed at a weight ratio of 20:80 to prepare organic solvent I-5. Light-emitting layer-forming solid component I-1 was dissolved in organic solvent I-5 to give 1.7 wt % to prepare light-emitting layer-forming composition I-5.

[0472] A light-emitting layer I-5 was formed in the same manner as in Reference Example 1 except that the light-emitting layer-forming composition I-5 was used instead of the light-emitting layer-forming composition I-1. The flatness of the light-emitting layer I-5 was evaluated in the same manner. The flatness of the light-emitting layer I-5 was 42.4% when calculated using the above definition. The distribution of the light-emitting layer I-5 and the blank is shown in FIG. Figure 5 .

[0473] <Results of Reference Examples 1 and 2 and Comparative Examples 1 to 3>

[0474] Table 2 shows the combinations of solvents and flatness in Reference Examples 1 and 2 and Comparative Examples 1 to 3.

[0475] [Table 2]

[0476]

[0477] <Inspection>

[0478] In Reference Examples 1 and 2, the distribution clearly demonstrates that, in addition to the improvement in the flattened area, the wetting rise (hereinafter referred to as the meniscus) toward the partition wall of the opening is extremely small, thus widening the effective area of ​​the light-emitting element. By selecting the flow activation energy within an appropriate range, it is possible to suppress unnecessary flow of the liquid and obtain a flat organic film.

[0479] In Comparative Examples 1 and 2, solvents with very low flow activation energy were used, so during the drying process, the liquid flowed toward the partition walls, widening the meniscus. Furthermore, the liquid moved from the center toward the partition walls, resulting in a thinner film thickness than in Reference Examples 1 and 2, even with the same droplet.

[0480] In Comparative Example 3, an organic solvent was designed with a very high flow activation energy. While this method can suppress flow, it is speculated that the meniscus widens during the drying process because the liquid film does not wet and descend. In other words, to achieve a flat organic film, fluidity is required to reduce liquid wetting during the initial drying phase. Meanwhile, fluidity must be eliminated at the end of the drying phase to prevent unnecessary liquid flow.

[0481] According to the comparison between the above-mentioned Reference Examples 1 and 2 and Comparative Examples 1 to 3, although Reference Examples 1 and 2 have excellent flatness of the opening portion, these Reference Examples 1 and 2 use a solvent with a boiling point less than 245°C as the second solvent. Therefore, as shown in Comparative Example 4 described later, the flatness of the panel end is significantly poor.

[0482] [Evaluation II: Evaluation of Flatness of the Panel Center]

[0483] <Preparation of Substrate II>

[0484] Substrate II having at least 21 openings in the major axis direction and 65 openings in the minor axis direction with a length of about 170 μm in the major axis direction and about 50 μm in the minor axis direction was prepared in the same manner as substrate I in Evaluation I.

[0485] <Preparation of solid components>

[0486] The hole transport material P-1 and the electron-withdrawing dopant D-2 shown below were mixed at a weight ratio of 100:10 to prepare a solid component II-1.

[0487]

[0488] <Definition of Flatness>

[0489] When the length of the opening is La, the average film thickness Da of the region where the distance x from the opening end satisfies 0.25<x / La<0.75 is calculated, and the region where the film thickness Do(x) of the organic film at a certain position x satisfies the following formula 2 is defined as Lb.

[0490] Da-Da×5%<Do(x)<Da+Da×5% (Formula 2)

[0491] With respect to the length La of the opening, the flatness is defined as Lb / La×100(%).

[0492] <Example 1>

[0493] 2-Isopropylnaphthalene was adjusted so that the ratio of solid component II-1 became 5 wt %, and heated at 110° C. for 3 hours while stirring at 420 rpm using a stirrer to prepare a standard composition II-1.

[0494] Standard composition II-1, 2-isopropylnaphthalene, and 2-ethylhexyl benzoate were mixed at a weight ratio of 50:20.75:29.25, respectively, stirred for a predetermined period, and then filtered through a 0.2 μm pore size membrane filter to prepare composition II-1. Composition II-1 had a solids concentration of 2.5% by weight and a weight ratio of 2-isopropylnaphthalene to 2-ethylhexyl benzoate of 70:30.

[0495] Using an inkjet printer (DMP-2831 manufactured by Fujifilm Corporation), composition II-1 was applied to the openings of substrate II, and vacuum dried to obtain an organic film. The organic film was calcined on a hot plate at 130°C for 3 minutes, and then calcined on a hot plate at 230°C for 30 minutes to form an organic film II-1. The coating amount was adjusted so that the dry film thickness was approximately 100 nm. 21 openings in the longitudinal direction and 65 openings in the short axis direction were coated, and a pattern of 1 uncoated for every 5 coated openings in the short axis direction was coated to form pixel group 1. Thus, pixel group 1 becomes a periodic structure in which the coated openings and the uncoated openings are repeated with 6 openings as a period in the short axis direction.

[0496] To evaluate flatness, the film thickness distribution in the minor axis direction of the organic film II-1 was measured using a stylus-type surface height difference meter (ET200 manufactured by Kosaka Laboratory). The measured openings were located at the following two locations within the surface of the 21×65 pixel group 1.

[0497] Measurement location 1: Counting from both ends of the major axis and minor axis, the 11th opening on the major axis and the 33rd opening on the minor axis (center area of ​​pixel group 1)

[0498] Measurement location 2: Counting from the ends of both the major and minor axes, the location of the third opening on the major axis and the ninth opening on the minor axis (edge ​​area of ​​pixel group 1)

[0499] The flatness evaluation results of the measurement site 1 are shown in Figure 7 The flatness evaluation results of the measurement site 2 are shown in Figure 8 Calculating the flatness of the organic film 1 at the two locations described above based on the definition of flatness in Equation 2 yields a flatness of 81.0% for measurement location 1 and 84.3% for measurement location 2, indicating excellent flatness. Furthermore, the film shapes at measurement locations 1 and 2 are approximately the same.

[0500] <Example 2>

[0501] Butyl benzoate was adjusted so that the ratio of solid component II-1 became 5% by weight, and the mixture was heated at 110° C. for 3 hours while being stirred at 420 rpm using a stirrer to prepare a standard composition II-2.

[0502] Composition II-2 was prepared by mixing standard composition II-2, butyl benzoate, and 2-ethylhexyl benzoate in a weight ratio of 50:20.75:29.25, respectively. Composition II-2 contained a solids component II-1 at a concentration of 2.5% by weight and a weight ratio of butyl benzoate to 2-ethylhexyl benzoate of 70:30.

[0503] Using composition II-2, an organic film II-2 was formed by the same procedure as in Example 1, and the flatness was evaluated.

[0504] The flatness evaluation results of the measurement site 1 are shown in Figure 9 The flatness evaluation results of the measurement site 2 are shown in Figure 10 Calculating the flatness of the organic film II-2 at the two locations described above based on the definition of flatness in Equation 2 yields a flatness of 55.8% at measurement location 1 and 58.7% at measurement location 2, demonstrating excellent flatness. Furthermore, the film shapes at measurement locations 1 and 2 are approximately the same.

[0505] <Example 3>

[0506] Composition II-3 was prepared by mixing standard composition II-1, 2-isopropylnaphthalene, 2-ethylhexyl benzoate, and benzyl benzoate in a weight ratio of 50:20.75:29.25, respectively. The mixture was stirred for a predetermined period of time and then filtered through a 0.2 μm membrane filter. Composition II-3 contained a solid component II-1 at a concentration of 2.5% by weight and a weight ratio of 2-isopropylnaphthalene, 2-ethylhexyl benzoate, and benzyl benzoate of 70:20:10.

[0507] An organic film II-3 was formed using composition II-3 by the same procedure as in Example 1, and its flatness was evaluated.

[0508] The flatness evaluation results of the measurement site 1 are shown in Figure 11 When the flatness of the organic film II-3 was calculated based on the definition of flatness in Formula 2, the flatness of the measurement site 1 was 90.2%, indicating good flatness.

[0509] <Comparative Example 4>

[0510] Standard composition II-1, 2-isopropylnaphthalene, and dibenzyl ether were mixed in a weight ratio of 50:20.75:29.25, respectively, stirred for a predetermined period, and then filtered through a 0.2 μm pore size membrane filter to prepare composition II-4. Composition II-4 contained a solid component II-1 concentration of 2.5% by weight and a weight ratio of 2-isopropylnaphthalene to dibenzyl ether of 70:30.

[0511] Using composition II-4, an organic film II-4 was formed by the same procedure as in Example 1, and the flatness was evaluated.

[0512] The flatness evaluation results of the measurement site 1 are shown in Figure 12 The flatness evaluation results of the measurement site 2 are shown in Figure 13 The flatness of the organic film II-4 at the two locations described above was calculated based on the definition of flatness in Formula 2. The flatness at measurement location 1 was 16.2%, while that at measurement location 2 was 31.5%, indicating that the film was not flat. The film at measurement location 1 and measurement location 2 had a concave center and did not have the same shape.

[0513] <Comparative Example 5>

[0514] The cyclohexylbenzene was adjusted so that the ratio of the solid component II-1 was 5% by weight, and the mixture was heated at 110° C. for 3 hours while being stirred at 420 rpm using a stirrer to prepare a standard composition II-3.

[0515] Composition II-5 was prepared by mixing standard composition II-3, cyclohexylbenzene, and 2-ethylhexyl benzoate in a weight ratio of 50:20.75:29.25, respectively. Composition II-5 contained 2.5% by weight of solid component II-1 and a weight ratio of cyclohexylbenzene to 2-ethylhexyl benzoate of 70:30.

[0516] Using composition II-5, an organic film II-5 was formed by the same procedure as in Example 1, and the flatness was evaluated.

[0517] The flatness evaluation results of the measurement site 1 are shown in Figure 14 The flatness evaluation results of the measurement site 2 are shown in Figure 15 When the flatness of the organic film II-5 at the two locations is calculated based on the definition of flatness in Formula 2, the flatness of measurement location 1 is 68.9%, indicating good flatness, but the flatness of measurement location 2 is 4.1%, indicating an unflat film.

[0518] <Comparative Example 6>

[0519] The 2-ethylhexyl benzoate was adjusted so that the ratio of the solid component II-1 was 2.5% by weight, and the mixture was heated at 110° C. for 3 hours while being stirred at 420 rpm using a stirrer to prepare a composition II-6.

[0520] Using composition II-6, an organic film II-6 was formed by the same procedure as in Example 1, and the planarity was evaluated.

[0521] The flatness evaluation results of the measurement site 1 are shown in Figure 16 The flatness evaluation results of the measurement site 2 are shown in Figure 17 The flatness of the organic film II-6 at the two locations was calculated based on the definition of flatness in Formula 2. The flatness at measurement location 1 was 43.3%, while that at measurement location 2 was 53.4%, indicating that a flat film was not obtained. The film shapes at measurement locations 1 and 2 were approximately the same.

[0522] The results of Examples 1-3 and Comparative Examples 4-6 are summarized in Table 3. These results show that when the boiling point of the second solvent is 245°C or higher, equivalent flatness is achieved in the center and ends of the panel. In particular, when the boiling point of the second solvent is 260°C or higher, flatness exceeding 80% is achieved in both the center and ends of the panel.

[0523] [Table 3]

[0524]

[0525] ※The information in brackets is the boiling point (℃): Flow activation energy (kJ / mol)

[0526] While the present invention has been described in detail using specific embodiments thereof, it will be apparent to one skilled in the art that various modifications can be made therein without departing from the spirit and scope of the invention.

[0527] This application is based on Japanese Patent Application No. 2018-088327 filed on May 1, 2018, the entire contents of which are incorporated herein by reference.

[0528] Explanation of symbols

[0529] 1 substrate

[0530] 2 Anode

[0531] 3 Hole injection layer

[0532] 4 Hole transport layer

[0533] 5. Luminescent layer

[0534] 6 Hole blocking layer

[0535] 7 Electron Transport Layer

[0536] 8 Electron injection layer

[0537] 9 cathode

[0538] 10 Organic electroluminescent elements

Claims

1. A composition comprising a functional material and a first solvent and a second solvent, The first solvent is a water-insoluble aromatic solvent, The boiling point of the first solvent is higher than the boiling point of the second solvent, and the difference between the boiling points of the first solvent and the second solvent is 10° C. or more, The flow activation energy of the first solvent is 22 kJ / mol or more and 35 kJ / mol or less, The flow activation energy of the first solvent is greater than the flow activation energy of the second solvent by more than 5 kJ / mol, The content ratio of the first solvent is 5 to 50% by weight relative to the total amount of the first solvent and the second solvent. The total content of the first solvent and the second solvent is 90% by weight or more relative to the total amount of the solvent in the composition, The second solvent has a boiling point of 245° C. or higher. The first solvent and the second solvent are each any one of substituted or unsubstituted naphthalene, substituted or unsubstituted benzoic acid ester, and substituted or unsubstituted aromatic ether.

2. The composition according to claim 1, wherein The flow activation energy of the first solvent is greater than 23 kJ / mol.

3. The composition according to claim 1, wherein The flow activation energy of the first solvent is greater than 24 kJ / mol.

4. The composition according to claim 1, wherein The flow activation energy of the first solvent is 34 kJ / mol or less.

5. The composition according to claim 1, wherein The flow activation energy of the first solvent is 32 kJ / mol or less.

6. The composition according to claim 1, wherein The flow activation energy of the first solvent is 30 kJ / mol or less.

7. The composition according to any one of claims 1 to 6, wherein The content of the first solvent is 5% by weight or more and 50% by weight or less relative to the total amount of the solvent in the composition.

8. The composition according to any one of claims 1 to 6, wherein The content of the first solvent is 5% by weight or more and 30% by weight or less relative to the total amount of the solvent in the composition.

9. The composition according to any one of claims 1 to 6, wherein The content of the first solvent is 10% by weight or more and 50% by weight or less relative to the total amount of the solvent in the composition.

10. The composition according to any one of claims 1 to 6, wherein The functional material is a low molecular weight material, and the molecular weight of the low molecular weight material is less than 10,000.

11. The composition according to claim 10, wherein The molecular weight of the low molecular weight material is 5000 or less.

12. The composition according to any one of claims 1 to 6, wherein The viscosity of the second solvent at 23° C. is 5 mPas or less.

13. The composition according to any one of claims 1 to 6, wherein The viscosity of the second solvent at 23° C. is 4.5 mPas or less.

14. The composition according to any one of claims 1 to 6, wherein The viscosity of the second solvent at 23° C. is 1.0 mPas or more.

15. The composition according to any one of claims 1 to 6, wherein The first solvent has a viscosity at 23° C. of 3 mPas or more and 20 mPas or less.

16. The composition according to any one of claims 1 to 6, wherein The difference between the boiling point of the first solvent and the boiling point of the second solvent is 25° C. or more.

17. The composition according to any one of claims 1 to 6, wherein The difference between the boiling point of the first solvent and the boiling point of the second solvent is 30° C. or more.

18. The composition according to any one of claims 1 to 6, wherein The boiling point of the first solvent is 400° C. or lower, and the boiling point of the second solvent is 370° C. or lower.

19. The composition according to claim 1, wherein The difference between the flow activation energy of the first solvent and the flow activation energy of the second solvent is 5.2 kJ / mol or more.

20. The composition according to claim 1, wherein The difference between the flow activation energy of the first solvent and the flow activation energy of the second solvent is 5.5 kJ / mol or more.

21. The composition according to claim 1, wherein The difference between the flow activation energy of the first solvent and the flow activation energy of the second solvent is 21.0 kJ / mol or less.

22. The composition according to claim 1, wherein The difference between the flow activation energy of the first solvent and the flow activation energy of the second solvent is 20.0 kJ / mol or less.

23. The composition according to any one of claims 1 to 6, wherein The surface tension of the first solvent is 30 mN / m or more.

24. The composition according to any one of claims 1 to 6, wherein The surface tension of the first solvent is 45 mN / m or less.

25. The composition according to any one of claims 1 to 6, wherein The first solvent is any one of 2-ethylhexyl benzoate, benzyl benzoate, acetylnaphthalene, dimethyl phthalate, and diethyl phthalate. The second solvent is any one of methylnaphthalene, ethylnaphthalene, isopropylnaphthalene, methoxynaphthalene, butyl benzoate, and pentyl benzoate.

26. The composition according to claim 25, wherein The combination of the first solvent and the second solvent is a combination of 2-ethylhexyl benzoate and methylnaphthalene, 2-ethylhexyl benzoate and ethylnaphthalene, 2-ethylhexyl benzoate and isopropylnaphthalene, 2-ethylhexyl benzoate and butyl benzoate, 2-ethylhexyl benzoate and isoamyl benzoate, benzyl benzoate and methylnaphthalene, benzyl benzoate and ethylnaphthalene, benzyl benzoate and isopropylnaphthalene, benzyl benzoate and butyl benzoate, or benzyl benzoate and isoamyl benzoate.

27. A method for producing an organic electroluminescent element, comprising the step of wet film formation using the composition according to any one of claims 1 to 26.

Citation Information

Patent Citations

  • Organic electroluminescent device having inproved power conversion efficiency

    JP1984194393A

  • Organic electroluminescent element

    JP1993331459A

  • Organic electroluminescence element

    JP1994207169A

  • Organic electroluminescent element

    JP1995041759A

  • Two layer electron injection electrode used in electroluminescence device

    JP1998074586A